Fracturing fluid comprising polymer of sodium 2-acrylamido-2-methylpropanesulfonate in crystalline form and hydraulic fracturing method

A water-soluble polymer prepared by using sodium 2-acrylamido-2-methylpropanesulfonate in crystalline form solves the problem of insufficient viscosity enhancement of fracturing fluid under high salinity or high temperature conditions, achieving effective suspension of proppant and improving oil and gas production efficiency.

CN120917066APending Publication Date: 2025-11-07爱森集团
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202480020995.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-13
Filing Date
2024-03-13
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing fracturing fluids have reduced viscosity under high salinity or high temperature conditions, and traditional polymers cannot effectively support proppant, resulting in insufficient suspension performance of proppant in fractures, which affects the oil and gas production efficiency of unconventional reservoirs.

Method used

A water-soluble polymer prepared from sodium 2-acrylamido-2-methylpropanesulfonate (ATBS.Na) in crystalline form, combined with its high friction-reducing properties and good solubility, is used to prepare fracturing fluids to improve viscosity and proppant suspension.

Benefits of technology

It improves the viscosity-enhancing effect of fracturing fluid in salt solutions, reduces polymer usage, lowers greenhouse gas emissions, enhances the suspension capacity of proppant in fractures, and improves oil and gas production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005607681180000061
    Figure BDA0005607681180000061
  • Figure BDA0005607681180000221
    Figure BDA0005607681180000221
  • Figure BDA0005607681180000231
    Figure BDA0005607681180000231
Patent Text Reader

Abstract

The present invention relates to a fracturing fluid comprising at least one proppant and at least one water-soluble polymer obtained from the sodium 2-acrylamido-2-methylpropanesulfonate salt ATBS.Na in crystalline form. The invention also relates to a method for preparing said fluid, and to a hydraulic fracturing method using said fluid.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a fracturing fluid comprising at least one proppant and at least one water-soluble polymer prepared from 2-acrylamido-2-methylpropane sulfonic acid sodium salt in crystalline form.

[0002] The present invention also relates to a method for hydraulic fracturing of a non-conventional subterranean hydrocarbon reservoir (oil and / or gas) using said fluid. BACKGROUND

[0003] The production of hydrocarbons (oil and / or gas) contained in non-conventional subterranean reservoirs has been developed for many years and requires the opening of fractures in the reservoir to carry out an economic production of hydrocarbons.

[0004] In the prior art and the rest of the description of the invention, the term "non-conventional subterranean reservoir" or "non-conventional reservoir" refers to deposits that require specific exploitation techniques, since they do not exist in the form of accumulations in porous and permeable rocks (see L'hydrocarbures de roche-mère en France Rapport provisoire - CGIET n°2011-04-G - Sustainable Development, Transport and Housing - April 2011). For non-conventional gas reservoirs, mention can be made of shale gas, coal bed gas or tight gas. For non-conventional oil reservoirs, mention can be made of heavy oil, shale oil or tight oil.

[0005] The reserves contained in non-conventional reservoirs are very substantial and extremely widespread in areas that were previously not exploitable (for example hydrocarbon source rocks such as shales, tight gas and coal gas). In the United States, shale gas is being widely exploited, which currently represents 46% of all natural gas production in the United States, compared to 28% in 1998. Very extensive basins are being drilled, known as the Barnett shale, the Ville Fayette shale, the Mowry shale, the Marcellus shale, the Utica shale... The development of drilling techniques has made it possible to exploit tight reservoirs.

[0006] Indeed, the production techniques have evolved from vertical wells to horizontal wells, which reduces the number of production wells required and their footprint on the ground, and makes it possible to better cover the volume of the reservoir to recover as much natural gas or oil as possible. However, the permeability is not sufficient to allow the easy migration of the hydrocarbons from the source rock to the well, thus making it possible to produce natural gas or oil in large quantities economically. It is therefore necessary to increase the permeability and the production operating face by stimulation operations, in particular by hydraulic fracturing of the rock in contact with the well.

[0007] Hydraulic fracturing

[0008] The purpose of hydraulic fracturing is to create additional permeability and to create a larger gas or oil production operation. Indeed, the natural barriers of low permeability, tight layers and the water resistance of drilling operations greatly limit the production. The natural gas or oil contained in unconventional reservoirs does not easily migrate from the rock to the well without stimulation measures.

[0009] These hydraulic fracturing operations of horizontal wells began in Appalachia in 1960 and have now been performed tens of thousands of times in the United States.

[0010] The research, reservoir modeling, drilling, cementing and stimulation techniques have become more and more complex, the equipment implemented is able to perform these operations in increasingly short times and to accurately analyze the results.

[0011] Stimulation of reservoirs by hydraulic fracturing

[0012] These operations consist in injecting water at high pressure and very high flow rate in order to create cracks distributed perpendicularly to the production well. This procedure is usually performed in several steps in order to create cracks along the entire length of the horizontal well, which makes it possible to cover the largest volume of reservoir.

[0013] In order to keep these cracks open, proppants (such as sand, plastic or calibrated ceramic) are added to prevent the cracks from closing and to maintain the capillary action created after the injection stop.

[0014] Due to the low viscosity of water, water alone is not sufficient to obtain a good proppant placement efficiency. This limits its ability to keep the proppants in place in the cracks. To solve this problem, fracturing fluids containing a viscosifying compound have been developed.

[0015] By definition, a compound is considered (in the description of the prior art and of the application) to be viscosifying when it increases the viscosity of the solution in which it is dissolved.

[0016] In addition to having viscosifying properties, the compound must also have specific rheological properties. Indeed, the compound must be able to create a low viscosity in order not to interfere with the transport and pumping of the fluid containing the proppants during the high shear forces experienced during the injection of the fracturing fluid. After the injection is complete, this same compound must be able to create a sufficient viscosity to support the proppants to keep them in the cracks when the shear decreases.

[0017] The viscosifying compound, which is generally a polymer, must therefore provide shear thinning properties to the solution in order to have a relatively low viscosity during the injection (under high shear) and a high viscosity when the shear decreases in order to keep the proppants suspended in the cracks.

[0018] The viscoelasticity of the polymer in solution should also be considered. This viscoelasticity and its importance in the application are described in the document SPE 147206 (Fracturing Fluid Comprised of Components Sourced Solely from the Food Industry Provides Superior Proppant Transport - David Loveless, Jeremy Holtsclaw, Rajesh Saini, Phil Harris, and Jeff Fleming, SPE, Halliburton) by visual observation in static or dynamic experiments, or by rheological measurements (for example, measurements of the viscous modulus and the elastic modulus (G' and G")) or rheometer measurements of the viscosity as a function of shear. Thus, the elasticity will be advantageous to ensure the transport and suspension of the fracturing proppant.

[0019] The choice of polymer is therefore not obvious and requires thorough rheological studies to obtain satisfactory results.

[0020] Among the viscosifying compounds of aqueous solution belonging to the prior art, mention can be made of natural substances such as guar gum and its derivatives, for example hydroxypropyl guar (HPG) or carboxymethyl hydroxypropyl guar (CMHPG); cellulose derivatives such as carboxymethyl cellulose or hydroxyethyl cellulose. These compounds are specifically described in U.S. Patents Nos. 4,033,415, 3,888,312 and 4,801,389. The latest developments in the performance of fracturing fluids are discussed in detail in the document SPE 152596 (Hydraulic Fracturing 101 : What Every Representative, Environmentalist, Regulator, Reporter, Investor, University Researcher, Neighbor and Engineer Should Know About Estimating Frac Risk and Improving Frac Performance in Unconventional Gas and Oil Wells - George E. King, Apache Corporation).

[0021] However, these natural substances, in particular guar derivatives, can also be used for other applications (for example the food industry or the textile industry) and the rush to exploit oil and gas resources from unconventional reservoirs competes with these other applications. This puts pressure on the availability of these products and leads to cost problems.

[0022] Other compounds derived from petrochemical products can have viscosifying properties. Synthetic polymers can be mentioned. Poly(meth)acrylamides, optionally partially hydrolyzed, and poly(meth)acrylates and polymers thereof are particularly known. These polymers generate viscosity in particular due to their molar mass and the interchain ionic repulsion. These polymers are described in patent GB 951 147, U.S. Pat. No. 3,727,689, U.S. Pat. No. 3,841,402 or U.S. Pat. No. 3,938,594. The mechanism of control of the viscosity is related to the increase in the hydrodynamic volume by interchain and intrachain repulsion, interchain entanglement, etc.

[0023] However, in the presence of high salinity or high use temperatures, these polymers do not generate strong entanglements and repulsions, which leads to a substantial decrease in their viscosifying capacity, especially after shearing experienced during the pumping step. In addition, these polymers generally do not have sufficient viscoelasticity to support the proppants in the fractures. It is necessary to increase the dose of these polymers to high levels to obtain the suspension properties of the proppants. However, the dose levels are not economically viable.

[0024] The polymers with viscosifying properties used can also advantageously act as friction reducers, which makes it possible to reduce the load drop in turbulent media and substantially increase the flow rate under the same power and pipe diameter.

[0025] Synthetic polymers based on 2-acrylamido-2-methylpropanesulfonic acid sodium have interesting friction-reducing properties in aqueous solution. These polymers are also known for their resistance to shear and thermal degradation, especially in salt solutions. However, obtaining very high molecular weight polymers based on 2-acrylamido-2-methylpropanesulfonic acid sodium is difficult, not to mention the solubility problems of these polymers when their molecular weight increases. However, to obtain the best friction-reducing phenomenon and high viscosity generation, it is essential that the polymer dissolves quickly, especially in salt solutions, and that it has a very high molecular weight. SUMMARY

[0026] The applicant has discovered and developed a fracturing fluid that can have a very high friction-reducing effect while ensuring an improved viscosifying effect in salt solutions (brines) or non-salt solutions (water).

[0027] Moreover, the good solubility of the fracturing fluid polymer, combined with its sulfonic anion nature, makes it possible to avoid its adsorption on the rock, which leads to a recovery of the electrical conductivity, thus increasing the hydrocarbon production (oil and / or gas). The oil (or oils) coming from the subterranean reservoir is also known as petroleum. It is usually a mixture of hydrocarbons.

[0028] According to the present application, the better performance of the polymer-containing fracturing fluid obtained from the crystalline form of 2-acrylamido-2-methylpropane sulfonic acid sodium salt (herein referred to as ATBS.Na) allows to reduce the amount of product (in particular polymer) needed, thus reducing the total water consumption and the emission of greenhouse gases (such as CO2).

[0029] A first aspect of the present application relates to a fracturing fluid comprising at least one proppant and at least one water-soluble polymer obtained from the crystalline form of ATBS.Na.

[0030] A second aspect of the present application relates to a method for producing a fracturing fluid having at least one water-soluble polymer obtained from the crystalline form of ATBS.Na.

[0031] A third aspect of the present application relates to a method for hydraulic fracturing of a subterranean unconventional reservoir of oil or gas using a fracturing fluid according to the present application.

[0032] A fourth aspect of the present application relates to a method for reducing the friction using a fracturing fluid in an operation of hydraulic fracturing of a subterranean unconventional reservoir of oil or gas using a fracturing fluid according to the present application.

[0033] The term "polymer" should be understood as meaning a homopolymer or a copolymer. The term "copolymer" should be understood as meaning a polymer obtained from at least two different monomers. It can thus be a copolymer of at least two monomers chosen from anionic monomers, cationic monomers, non-ionic monomers, zwitterionic monomers, hydrophobic monomers and mixtures thereof.

[0034] The term "hydrophilic monomer" should be understood as meaning a monomer having an octanol-water partition coefficient K ow of equal to or less than 1, measured at 25°C in a mixture of octanol-water in a volume ratio of 1 / 1 at a pH of 6 to 8. ow

[0035] The term "hydrophobic monomer" should be understood as meaning a monomer having an octanol-water partition coefficient K ow of more than 1, measured at 25°C in a mixture of octanol-water in a volume ratio of 1 / 1 at a pH of 6 to 8. ow

[0036] ​​The term "crystal" or "crystalline form" refers to a solid material whose constituents (e.g., atoms, molecules, or ions) are arranged in a highly ordered microscopic structure, forming a crystal lattice that extends in all directions. It does not include amorphous solids.

[0037] Octanol-water partition coefficient K ow represents the ratio of the concentration of monomer (g / L) between the octanol phase and the water phase. It is defined as follows:

[0038] [Calculation 1]

[0039]

[0040] By definition, a water-soluble polymer is a polymer that, when stirred into water at 25°C at a concentration of 50 g.L -1 , gives rise to an aqueous solution that is free of insoluble particles.

[0041] "X and / or Y" is to be understood as meaning "X", or "Y", or "X and Y".

[0042] The present application also includes all possible combinations of the various embodiments disclosed, whether they are preferred embodiments or given as examples. Furthermore, when numerical ranges are indicated, the limit values are included in these ranges. The present disclosure also includes all combinations of limit values between these numerical ranges. For example, the disclosure of the numerical range "1-20, preferably 5-15" means the ranges "1-5", "1-15", "5-20" and "15-20" as well as the values 1, 5, 15 and 20.

[0043] Crystalline form of ATBS.Na

[0044] The crystalline form of ATBS.Na has an X-ray powder diffraction pattern comprising peaks at the following positions: 11.7°; 12.2°; 13.2°; 13.5°; 15.6°; 16.8°; 17.8°; 18.5°; 19.1°; 20.6°; 21.4°; 23.3°; 25.1°; 25.8°; 26.9°; 29.1°; 29.5°; 31.0°; 33.0°; 33.6°; 34.4°; 35.2°; 35.9°; 37.1°; 38.4°; 39.6°; 41.1°; 42.9°; 45.1°; 46.0°; 47.2°; 47.6°. The uncertainty of these peaks is typically about + / - 0.1°.

[0045] X-ray crystallography, radiocrystallography or X-ray diffraction is an analytical technique used to study the structure of crystalline substances on an atomic scale. It is based on the physical phenomenon of X-ray diffraction. A diffractometer with a copper source can be used.

[0046] The powder formed by a particular crystalline phase always shows diffraction peaks in the same direction. This diffraction pattern thus forms a true signature of the crystalline phase. It is thus possible to determine the nature of each crystalline phase in a mixture or a pure product.

[0047] This signature is specific to each organic or inorganic crystalline compound and is in the form of a series of peaks at 2 theta (2-theta) angles.

[0048] This technique is used to characterize a substance, in particular different crystalline forms that can exist for the same chemical molecule.

[0049] The crystalline form of ATBS.Na has a Fourier transform infrared spectrum comprising peaks at the following positions: 3576 cm -1 , 3485 cm -1 , 3310 cm -1 , 3079 cm -1 , 2975 cm -1 , 1658 cm -1 , 1629 cm -1 , 1543 cm -1 , 1403 cm -1 , 1321 cm -1 , 1301 cm -1 , 1205 cm -1 , 1187 cm -1 , 1163 cm -1 , 1046 cm -1 , 980 cm -1 , 629 cm -1 . The uncertainty of these peaks is generally about + / - 8 cm -1 .

[0050] The infrared measurements are made by Fourier transform, for example using a PerkinElmer Spectrum 100 spectrometer equipped with a single reflection ATR polarized accessory, with a precision of 8 cm -1 .

[0051] The Fourier transform infrared spectrum is an analysis of the vibrations emitted, absorbed or scattered by the molecules. This technique is sensitive to so-called short interactions (influence of the unit grid on the bond). In most cases, the Fourier transform infrared spectra of different crystalline systems are significantly different. The Fourier transform infrared spectrum thus reflects the details of the crystal structure of a compound.

[0052] Generally, unless otherwise stated, the X-ray diffraction patterns and infrared spectra are obtained at 20°C, at 1 absolute atmosphere (101,325 Pa).

[0053] The minimum ignition energy of the crystalline form of ATBS.Na is greater than 500 mJ, preferably greater than 1000 mJ (1 mJ = 10 -3 Joule).

[0054] The minimum ignition energy represents the minimum energy that must be supplied to the product (compound) to make it ignite. This energy can be electrical or thermal. The minimum ignition energy is a crucial piece of information when considering the risk of explosion during the handling (transfer, storage, reaction, shaping, etc.) of the product.

[0055] The minimum ignition energy depends on the nature of the powder (composition) and its macromolecular structure (particle size, crystalline form, specific surface area).

[0056] In the case of solids, this energy is the minimum energy of an electric spark that can ignite a cloud of dust. The higher the minimum ignition energy value, the less risk there is of the solid igniting during use, handling or storage.

[0057] The minimum ignition energy is measured according to the standard NF EN 13821.

[0058] The crystalline form of ATBS.Na exhibits 4 thermal phenomena at 49.8°C, 144.8°C; 169.8°C and 254.3°C by differential scanning calorimetry technique. The uncertainty associated with the observation of these phenomena is generally about 10°C, advantageously 5°C or less.

[0059] The thermal phenomena are measured by differential scanning calorimetry (DSC). This technique uses the measurement of the thermal variations associated with the thermal denaturation of the compound when heated at a constant speed, for example at a ramp rate of 10°C / minute.

[0060] Process for producing a crystalline form of a sodium salt

[0061] The process for producing a crystalline form of ATBS.Na comprises at least the following successive steps:

[0062] 1) mixing 2-acrylamido-2-methylpropane sulfonic acid with an aqueous solution SA1 and at least one sodium salt base, advantageously for at least 1 minute, to form an aqueous solution or aqueous suspension SA2;

[0063] 2) distilling the aqueous solution or aqueous suspension SA2 at a pressure of 700 mbar or less to form a suspension S1 ;

[0064] 3) subjecting the suspension S1 to a solid-liquid separation and separating the crystals in the form of a composition C1 of the suspension S1 obtained at the end of step 2).

[0065] The crystals obtained are a crystalline form of ATBS.Na.

[0066] In step 1), the "sodium salt base" is understood to mean at least one inorganic sodium salt a base, such as sodium hydroxide, sodium carbonate, sodium bicarbonate or a mixture thereof.

[0067] The temperature and the mixing time of step 1) can vary in particular as a function of the concentration of 2-acrylamido-2-methylpropanesulfonic acid (ATBS). The person skilled in the art knows how to adjust the temperature variation and the mixing time to optimize the formation of crystals.

[0068] The method for producing the sodium salt in crystalline form can be carried out on ATBS in any form (for example, in acicular form or in hydrated form).

[0069] The production method can be carried out on ATBS in any purity.

[0070] The method can thus be carried out downstream of any type of method for producing ATBS. It can also be carried out on ATBS crystals that have already been obtained.

[0071] Step 1) of the method for producing the sodium salt in crystalline form:

[0072] ATBS is produced by the production method as described previously (acrylonitrile, fuming sulfuric acid and isobutene). ATBS can be in the form of a fine powder, or shaped in a controlled manner by a method such as pressing, granulation or extrusion.

[0073] ATBS can be added to the aqueous solution SA1 before, after or in parallel with the addition of the sodium salt base, preferably in parallel. Preferably, the aqueous solution SA1 is water.

[0074] The sodium salt base can be added in the form of an aqueous solution. In this case, the sodium salt base aqueous solution can be partly or totally the aqueous solution SA1.

[0075] Advantageously, the concentration of ATBS sodium salt in the aqueous solution or aqueous suspension SA2 is between 1% and saturation by weight, preferably between 10% and saturation by weight, more preferentially between 20% and saturation by weight, more preferentially between 30% and saturation by weight, more preferentially between 40% and saturation by weight, even more preferentially between 50% and saturation by weight, relative to the weight of the aqueous solution or aqueous suspension SA2.

[0076] ATBS and the sodium salt base can be added all at once or in several stages. They are preferably added in several stages. They are preferably added all at once.

[0077] When they are added in several stages, ATBS and the sodium salt base are added in batches.

[0078] When ATBS and the sodium salt base are added in batches, there is no limit to the number of batches, advantageously there are at least two batches, preferably at least three batches.

[0079] There is no restriction on the order of addition of ATBS and sodium salt base. They can be added simultaneously (i.e. in parallel), one after the other (ATBS is added first, then sodium salt base, or vice versa), or alternately (a first portion of ATBS is added, then a first portion of sodium salt base, followed by a second portion of ATBS, then a second portion of sodium salt base, etc.); they are preferably added simultaneously.

[0080] When they are added one after the other or alternately, the second compound (whether ATBS or sodium salt base) can start to be added before the addition of the first compound is complete.

[0081] The first portion Fi of ATBS advantageously represents at least 1 mol%, preferably at least 5 mol%, more preferably at least 10 mol%, even more preferably at least 15 mol%, even more preferably at least 20 mol% of the total amount of ATBS present in the aqueous solution or aqueous suspension SA2.

[0082] The second portion F2 of ATBS advantageously represents at least 1 mol%, preferably at least 5 mol%, more preferably at least 10 mol%, even more preferably at least 15 mol%, even more preferably at least 20 mol% of the total amount of ATBS present in the aqueous solution or aqueous suspension SA2.

[0083] The third portion F3 of ATBS advantageously represents at least 1 mol%, preferably at least 5 mol%, more preferably at least 10 mol%, even more preferably at least 15 mol%, even more preferably at least 20 mol% of the total amount of ATBS present in the aqueous solution or aqueous suspension SA2.

[0084] In one particular embodiment, the process is carried out continuously, in which case ATBS and sodium salt base are added continuously.

[0085] The amount of ATBS in the aqueous solution or aqueous suspension SA2 is advantageously from 10 to 90% by weight, preferably from 20 to 85% by weight, more preferably from 30 to 80% by weight, relative to the total weight of the aqueous solution or aqueous suspension SA2.

[0086] The mixing (ATBS + sodium salt base) of step 1) is advantageously carried out at a temperature of from 0 to 90°C, preferably from 5 to 60°C, more preferably from 10 to 40°C, to obtain the aqueous solution or aqueous suspension SA2.

[0087] In one particular embodiment, the aqueous solution or aqueous suspension SA2 can comprise one or more organic solvents.

[0088] In some embodiments, the aqueous solution SA1 can comprise one or more organic solvents.

[0089] The amount of organic solvent can vary as a function of the temperature and the amount of ATBS or sodium salt base. This amount is not limited, provided that it does not prevent obtaining ATBS.Na in crystalline form. The person skilled in the art knows how to determine this limit, which is a routine task. Generally, the aqueous solution or aqueous suspension SA2 contains more water (by volume) than organic solvent.

[0090] The one or more organic solvents are advantageously chosen from the following compounds:

[0091] - an organic acid, advantageously a carboxylic acid comprising from 1 to 8 carbon atoms;

[0092] - an amide, advantageously comprising from 1 to 8 carbon atoms;

[0093] - an alcohol, advantageously comprising from 1 to 8 carbon atoms;

[0094] - a ketone, advantageously comprising from 3 to 8 carbon atoms;

[0095] - an ether, advantageously comprising from 2 to 8 carbon atoms;

[0096] - an ester, advantageously comprising from 2 to 8 carbon atoms;

[0097] - an alkane, advantageously comprising from 4 to 8 carbon atoms, preferably from 5 to 6 carbon atoms;

[0098] - a halogenated hydrocarbon compound, advantageously comprising from 1 to 8 carbon atoms;

[0099] - a nitrile, advantageously comprising from 1 to 8 carbon atoms; or

[0100] - a mixture thereof.

[0101] When the organic solvent is used in the application, the temperature can be adjusted so that the solvent + water mixture remains in liquid form.

[0102] These compounds can be linear or branched. They can be saturated or comprise unsaturated bonds. The unsaturated bonds correspond to double or triple bonds (for example C=C or C≡C).

[0103] The organic solvent is preferably chosen from acetonitrile, isopropyl alcohol, acrylic acid, acetic acid or a mixture thereof. The organic solvent is preferably acetonitrile.

[0104] At the temperature at which steps 2) and 3) are carried out, the organic solvent is generally in liquid form. In addition, it is advantageously partially miscible in water, preferably completely miscible in water.

[0105] If necessary, the organic solvent can be used to dissolve any impurities or by-products present with the ATBS used to form the aqueous solution or aqueous suspension SA2. However, the ATBS is not necessarily soluble in the solvent.

[0106] In a preferred embodiment according to the application, the aqueous solution or aqueous suspension SA2 does not contain organic solvents.

[0107] In a preferred embodiment according to the application, the aqueous solution SA1 does not contain organic solvents.

[0108] The time allowed for mixing the aqueous solution SA1 and ATBS is advantageously at least 1 minute, preferably 1 minute to 600 minutes, more preferably 5 minutes to 400 minutes, even more preferably 10 minutes to 240 minutes.

[0109] The compounds of step 1) can be mixed using a variety of techniques. Examples include, but are not limited to, reactors with stirrers, loop reactors, static mixers, microreactors, piston reactors, agitated filter dryers (such as Nutsche’s), paddle mixers, double-cone mixers, plowshare mixers, and disc mixers.

[0110] The pH in step 1) is advantageously controlled to be 6 to 14, preferably 8 to 14, more preferably 10 to 14, even more preferably 12 to 14, and even more preferably 13 to 14.

[0111] The amount of ATBS.Na in the aqueous solution or aqueous suspension SA2 is advantageously 10 to 90 wt.-%, preferably 20 to 90 wt.-%, preferably 30 to 90 wt.-%, preferably 50 to 90 wt.-%, preferably 20 to 85 wt.-%, more preferably 30 to 80 wt.-%, relative to the total weight of the aqueous solution or aqueous suspension SA2.

[0112] Step 2) of the process for producing ATBS sodium salt in crystalline form:

[0113] The distillation of the aqueous solution or aqueous suspension SA2 is carried out at a pressure of 700 mbar or less. It is usually carried out in a vacuum distillation apparatus, which is usually an evaporator. It is therefore also referred to as “vacuum distillation” herein.

[0114] When the aqueous solution or aqueous suspension SA2 is subjected to distillation, usually by passing it through an evaporator, crystals of ATBS.Na start to form. The crystalline solid particles of ATBS, at least one sodium salt base, and ATBS.Na thus coexist in the aqueous solution or aqueous suspension SA2.

[0115] The aqueous solution or aqueous suspension SA2 can be distilled using an evaporator. The evaporator can be a falling-film evaporator, or a rising-film evaporator, or a wiped-film evaporator, or a short-path evaporator, or a forced-circulation evaporator, or a spiral-tube evaporator, or a flash evaporator. It can also be a continuously stirred reactor. Preferably, the distillation is carried out in a wiped-film evaporator, a short-path evaporator, or a forced-circulation evaporator. Even more preferably, the distillation is carried out in a wiped-film evaporator.

[0116] Generally, the evaporator is a device comprising an inlet of the solution to be treated (aqueous solution or aqueous suspension SA2), an outlet of the distilled solvent (water and any organic solvent) and an outlet of the suspension S1.

[0117] The residence time (in other words, the distillation time) of the aqueous solution or aqueous suspension SA2 in the distillation device (advantageously under vacuum) (which is advantageously an evaporator) at a pressure of 700 mbar or less is advantageously comprised between 1 and 600 seconds, preferably between 3 and 300 seconds, more preferably between 30 and 100 seconds. The residence time corresponds to the time necessary to carry out step 2), i.e. the time necessary to prepare the suspension S1 by distilling the aqueous solution or aqueous suspension SA2. In other words, when an evaporator is used, this time is the residence time of the ATBS (and / or of the sodium salt of its crystalline form) between the inlet and the outlet of the device. This residence time depends on the amount of water (and any organic solvent), of ATBS and of sodium salt base present in the aqueous solution or aqueous suspension SA2. The skilled person knows how to adjust the residence time as a function of the amount of the constituents of the aqueous solution or aqueous suspension SA2 to obtain ATBS.Na in crystalline form.

[0118] The distillation can be carried out in a vertical evaporator or in a horizontal evaporator. Preferably, it is carried out in a vertical evaporator.

[0119] The aqueous solution or aqueous suspension SA2 can be circulated in co-current or counter-current with the steam produced by the evaporation. Preferably, it is circulated in counter-current with the steam in the distillation device (advantageously an evaporator). In other words, it is preferred to introduce the aqueous solution or aqueous suspension SA2 into the distillation device (advantageously an evaporator) in co-current or counter-current with the distilled solvent.

[0120] The aqueous solution or aqueous suspension SA2 can be circulated in one or more evaporators in series before obtaining the suspension S1. Preferably, it is circulated in a single evaporator.

[0121] The pressure during the distillation is advantageously comprised between 1 and 700 mbar absolute (1 mbar = 100 Pa). It is preferably less than 700 mbar absolute, more preferably less than 600 mbar absolute, more preferably less than 500 mbar absolute, more preferably less than 400 mbar absolute, more preferably less than 300 mbar absolute, more preferably less than 200 mbar absolute, more preferably less than 100 mbar absolute, even more preferably less than 50 mbar absolute and advantageously greater than 1 mbar absolute. The absolute pressure corresponds to the pressure relative to the zero pressure (vacuum).

[0122] Generally, the pressure during distillation is preferably from 10 to 700 mbar, preferably from 20 to 700 mbar, preferably from 40 to 700 mbar, more preferably from 50 to 600 mbar, more preferably from 50 to 500 mbar, more preferably from 50 to 400 mbar, more preferably from 50 to 300 mbar, more preferably from 100 to 700 mbar, more preferably from 200 to 700 mbar, more preferably from 500 to 700 mbar, more preferably from 40 to 100 mbar.

[0123] In one particular embodiment, step 2) comprises a step 2') (optional) to help the evaporation of the solvent. Step 2' consists in increasing the temperature of the aqueous solution or aqueous suspension SA2, in other words, the distillation according to step 2' is performed under heating.

[0124] In some embodiments, the aqueous solution or aqueous suspension SA2 is advantageously heated at a temperature from 5°C to 95°C, preferably more than 10°C to 60°C, more preferably more than 20°C to 40°C, in step 2).

[0125] The heating during distillation can be performed by various techniques. Examples include, but are not limited to, heating with steam, hot water, electricity, by vapor compression, or indeed using a heat pump. Thus, the distillation device can be of the double-walled type, a hot heat transfer fluid circulating between the two walls.

[0126] The aqueous solution or aqueous suspension SA2 is advantageously heated to a temperature of more than 5°C to 95°C, preferably more than 10°C to 60°C, more preferably more than 20°C to 40°C.

[0127] When the aqueous solution or aqueous suspension SA2 is heated, the temperature is advantageously greater than the temperature of step 1).

[0128] The temperature of the aqueous solution or aqueous suspension SA2 is advantageously increased at a rate of from 0.1 to 10°C / hour, preferably from 0.2 to 9°C / hour, more preferably from 0.3 to 8°C / hour, even more preferably from 0.5 to 5°C / hour.

[0129] In some embodiments, the temperature of the aqueous solution or aqueous suspension SA2 is advantageously increased at a rate of from 10 to 150°C / hour, preferably from 30 to 110°C / hour, more preferably from 50 to 100°C / hour, even more preferably from 60 to 90°C / hour.

[0130] The increase in temperature can not be constant throughout the process. For example, the aqueous solution or aqueous suspension SA2 can be heated at a rate of 5°C per hour for the first 3 hours, then at a rate of 10°C per hour until the final temperature is reached.

[0131] According to another particular embodiment of the application, step 2) can comprise a step 2" (optional) (which is after step 2') or instead of step 2' ), step 2" helps to increase the yield and profitability of the process of the application by accelerating the crystallization of the sodium salt of ATBS into its crystalline form. Step 2" consists in lowering the temperature of the aqueous solution or aqueous suspension SA2.

[0132] The aqueous solution or aqueous suspension SA2 is advantageously cooled to a temperature comprised between 5°C and less than 95°C, preferably between 10°C and less than 60°C, more preferably between 20°C and less than 40°C, even more preferably between 10°C and 40°C.

[0133] In some embodiments, step 2) further comprises a cooling step.

[0134] The cooling step is advantageously performed at a temperature comprised between 5°C and 95°C, preferably more than 10°C and 60°C, more preferably more than 10°C and 40°C.

[0135] In some embodiments, the temperature of the cooling step is increased at a rate comprised between 0.1 and 8°C / hour, preferably between 0.2 and 8°C / hour, more preferably between 0.3 and 8°C / hour, even more preferably between 0.5 and 5°C / hour.

[0136] In some embodiments, the temperature of the cooling step is advantageously lower than the heating temperature of step 2) and / or step 1).

[0137] In some embodiments, the cooling step is performed on the aqueous solution or aqueous suspension SA2 and / or on the concentrated aqueous solution or aqueous suspension SA2 and / or on the suspension S1.

[0138] When the aqueous solution or aqueous suspension SA2 is cooled (step 2"), the temperature is advantageously lower than the temperature of step 2) and optionally 2').

[0139] According to a preferred embodiment, the temperature of step 2") is equal to or lower than the temperature of step 1).

[0140] In some embodiments, no organic solvent or aqueous solution is added in step 2" to obtain crystals of ATBS.Na.

[0141] The temperature of the aqueous solution or aqueous suspension SA2 is advantageously decreased at a rate comprised between 0.1 and 8°C / hour, preferably between 0.2 and 8°C / hour, more preferably between 0.3 and 8°C / hour, even more preferably between 0.5 and 5°C / hour.

[0142] The decrease of the temperature can not be constant throughout the process. For example, the aqueous solution or aqueous suspension SA2 can be cooled at a rate of 5°C per hour during the first 3 hours and then at a rate of 8°C per hour until the final temperature is reached.

[0143] When the aqueous solution or aqueous suspension SA2 is cooled, crystals of ATBS.Na and a suspension S1 are obtained.

[0144] In a particular embodiment, crystals of ATBS.Na previously obtained can be added in this step to modify the composition of the suspension S1. This is a kind of crystallization seed that makes it possible to better control the crystallization temperature, the particle size of the crystals, the particle size distribution, the purity of the final product and possibly the yield. The crystals of sodium salt of ATBS added in this way have an X-ray powder diffraction pattern comprising peaks at the following positions: 11.7°; 12.2°; 13.2°; 13.5°; 15.6°; 16.8°; 17.8°; 18.5°; 19.1°; 20.6°; 21.4°; 23.3°; 25.1°; 25.8°; 26.9°; 29.1°; 29.5°; 31.0°; 33.0°; 33.6°; 34.4°; 35.2°; 35.9°; 37.1°; 38.4°; 39.6°; 41.1°; 42.9°; 45.1°; 46.0°; 47.2°; 47.6° 2q (+ / - 0.1°).

[0145] According to a particular embodiment of the application, the solvent distilled in step 2) can be partially or totally recycled to form the aqueous solution or aqueous suspension SA2 of step 1). In other words, the distilled solvent is advantageously at least partially recycled into the aqueous solution SA2.

[0146] According to another particular embodiment of the application, in the optional step 4) (with or without a pre-treatment step), the distilled solvent can be partially or totally recycled, generally to wash the crystals of ATBS sodium salt obtained after the step 3) of solid-liquid separation.

[0147] The suspension S1 obtained advantageously comprises from 30 to 90% by weight of ATBS.Na in crystalline form relative to the total weight of the suspension S1, preferably from 50 to 90% by weight, more preferentially from 30 to 80% by weight, preferably from 50 to 60% by weight of ATBS.Na in crystalline form relative to the total weight of the suspension S1.

[0148] During step 2), the pH is advantageously greater than 10, preferentially greater than 11, more preferentially greater than 12, and even more preferentially between 13 and 14.

[0149] Step 3) of the process for producing ATBS sodium salt in crystalline form:

[0150] The crystals of ATBS sodium salt contained in the suspension S1 obtained at the end of step 2) are separated in a solid-liquid separation step and are in the form of a composition C1.

[0151] The solid-liquid separation step can be performed using a variety of techniques. Examples include, but are not limited to, the use of a centrifuge, a decanter, a filter press, a stirred filter, a belt filter, a disc filter or a rotary drum filter. The solid-liquid separation is preferably performed using a centrifuge. The solid-liquid separation can be performed by gravity sedimentation.

[0152] Step 3) is advantageously performed at a temperature ranging from -20°C to 40°C, preferably from -5°C to 30°C.

[0153] After step 3) of solid-liquid separation, the ATBS sodium salt crystals are preferably not dried.

[0154] The ATBS sodium salt crystals content of the separated composition C1 is advantageously from 40 to 99% by weight, preferably from 60 to 99% by weight, more preferably from 60 to 98% by weight, even more preferably from 80 to 99% by weight, relative to the weight of the composition C1. The remainder of the composition C1 can be water and / or soluble ATBS sodium salt, and possibly the sodium salt base introduced in step 1).

[0155] At the end of this step 3), the crystals are characterized as ATBS.Na crystals.

[0156] In one particular embodiment, all or part of the liquid phase obtained after the solid-liquid separation is used for the aqueous solution or aqueous suspension SA2 of step 1).

[0157] During step 4), the pH is advantageously controlled to be from 6 to 14, preferably from 8 to 14, more preferably from 10 to 14, even more preferably from 12 to 14, and even more preferably from 13 to 14.

[0158] Step 4) of the process for producing ATBS sodium salt in crystalline form:

[0159] In the optional step 4), the composition C1 containing ATBS.Na crystals obtained at the end of step 3) is washed using a washing solution.

[0160] The washing solution can be water, an aqueous solution of a sodium salt base (which can be saturated or not), or a solution of ATBS sodium salt (which can be saturated or not), and it is preferably a saturated solution of ATBS sodium salt.

[0161] Examples of sodium salt base solutions include solutions of sodium hydroxide, sodium carbonate, sodium bicarbonate or mixtures thereof.

[0162] The washing solution can comprise one or more organic solvents.

[0163] Advantageously, the washing solution does not comprise an organic solvent.

[0164] As already indicated in step 1), the organic solvent is advantageously selected from an organic acid, an amide, an alcohol, a ketone, an ether, an ester, an alkane, a halogenated hydrocarbon compound, a nitrile, or a mixture thereof. The organic solvent is preferably selected from acetonitrile, isopropanol, acetic acid or a mixture thereof. More preferably, the organic solvent is preferably acetonitrile.

[0165] In a particular embodiment, the composition C1 obtained at the end of step 3) is washed by spraying a washing solution on said composition C1.

[0166] In a particular embodiment, the composition C1 obtained at the end of step 3) is washed by suspending said composition C1 in a washing solution.

[0167] The weight ratio of the aqueous washing solution to the composition C1 obtained at the end of step 3) is advantageously comprised between 0.05:1 and 10:1, more preferably between 0.1:1 and 5:1.

[0168] The washing step is advantageously performed at a temperature comprised between -5°C and 40°C, preferably between 0°C and 30°C. The person skilled in the art knows how to adjust the temperature so that the ATBS.Na crystals do not dissolve.

[0169] The ATBS.Na crystals obtained at the end of the optional step 4) can be separated from the washing solution in the form of a composition C2 by a solid-liquid separation step.

[0170] The solid-liquid separation step can be performed using various techniques. Examples include, but are not limited to, the use of a vertical or horizontal centrifuge, a decanter, a filter press, a belt filter, a disc filter, a pusher filter or a drum filter. The solid-liquid separation can be performed by gravity sedimentation.

[0171] In a particular embodiment, all or part of the recovered washing solution can be reused in step 4) (with or without a pre-treatment step).

[0172] In a particular embodiment, all or part of the recovered washing solution can be used in the aqueous solution SA1 and / or in the aqueous solution or aqueous suspension SA2 in step 1) (with or without a pre-treatment step).

[0173] The pH of the washing solution of step 5) is advantageously controlled between 6 and 14, preferably between 8 and 14.

[0174] Step 5) of the process for producing ATBS.Na in crystalline form:

[0175] In the optional step 5), the composition C1 obtained at the end of step 3) or the composition C2 obtained at the end of step 4) is dried.

[0176] The drying step can be performed using a variety of techniques. Examples include, but are not limited to, using all convective, conductive or radiative drying techniques (fluidized bed dryer, through-bed dryer, conveyor belt drying, microwave, heated agitated filter, high frequency radiation, infrared radiation, spray).

[0177] The drying operation can be performed at atmospheric pressure or under vacuum.

[0178] The drying step can be performed discontinuously (batch drying) or continuously.

[0179] Other steps of the process for producing ATBS.Na in crystalline form:

[0180] At least one polymerization inhibitor can be introduced during the production process, i.e. during steps 1) to 5), and whatever the step, to prevent possible polymerization of ATBS or of its salts. The polymerization inhibitor can be chosen, in a non-limiting manner, from hydroquinone, p-methoxyphenol, phenothiazine, 2,2,6,6-tetramethyl(piperidin-1-yl)oxy, 4-hydroxy-2,2,6,6-tetramethyl(piperidin-1-yl)oxy, phenylenediamine derivatives, or mixtures thereof.

[0181] The polymerization inhibitor is preferably p-methoxyphenol or 4-hydroxy-2,2,6,6-tetramethyl(piperidin-1-yl)oxy.

[0182] The amount of polymerization inhibitor introduced is advantageously between 0.001 and 5% by weight, more preferentially between 0.01 and 1% by weight, relative to the amount of ATBS introduced in step 1).

[0183] The polymerization inhibitor can be introduced during any one or more steps of the process. Preferentially, an additional amount of polymerization inhibitor is introduced during step 1). More preferentially, the polymerization inhibitor is part of the aqueous solution SA1 introduced in step 1).

[0184] The production process (steps 1) to 5)) can be performed continuously or discontinuously (batch production).

[0185] Composition of the water-soluble polymer

[0186] The water-soluble polymer is obtained from ATBS.Na in crystalline form and advantageously from at least one other monomer which can be chosen from among hydrophilic non-ionic monomers and / or hydrophilic anionic monomers and / or hydrophilic cationic monomers and / or hydrophilic zwitterionic monomers and / or hydrophobic monomers and mixtures thereof. It can be a polymer of a variety of different monomers or a homopolymer.

[0187] Advantageously, the hydrophilic non-ionic monomer(s) that can be used in the present application are particularly chosen from the group comprising water-soluble vinyl monomers, such as acrylamide, methacrylamide, N-alkylacrylamides, N-alkylmethacrylamides, N,N-dialkylacrylamides, such as N,N-dimethylacrylamide or N,N-diethylacrylamide, N,N-dialkylmethacrylamides, alkoxylated esters of acrylic acid, N-vinylpyrrolidone, N-hydroxymethyl(meth)acrylamide, N-vinylcaprolactam, N-vinylformamide (NVF), N-vinylacetamide, N-vinylimidazole, N-vinylsuccinimide, acryloyl morpholine (ACMO), glycidyl methacrylate, vinyl acetate, glyceryl methacrylate, diacetone acrylamide, methacrylic anhydride, acrylonitrile, maleic anhydride, itaconamide, hydroxyalkyl (meth)acrylate, thioalkyl (meth)acrylate, isoprenol and its alkoxylated derivatives, hydroxyethyl (meth)acrylate and its alkoxylated derivatives, hydroxypropyl acrylate and its alkoxylated derivatives, and mixtures thereof. Among the non-ionic monomers, the alkyl groups are advantageously Ci-C5, more advantageously Ci-C3. They are preferably linear alkyl groups. Preferably, the hydrophilic non-ionic monomer is acrylamide.

[0188] The water-soluble polymer advantageously comprises from 0 to 99 mol%, preferably from 40 to 95 mol%, more preferably from 45 to 90 mol%, of hydrophilic non-ionic monomer(s).

[0189] Advantageously, the one or more hydrophilic anionic monomers that can be used in the present application, in addition to the crystalline form of ATBS.Na, can be chosen from a large group. These monomers can have a vinyl function (advantageously acrylic, maleic, fumaric, malonic, itaconic, or allyl) and contain a carboxylate, phosphonate, phosphate, sulfate or sulfonate group, or another anionic charged group. Examples of suitable monomers include acrylic acid; methacrylic acid; dimethylacrylic acid; itaconic acid; C1-C3 half esters of itaconic acid; acryloyl chloride; crotonic acid; maleic acid; fumaric acid; 3-acrylamido-3-methylbutanoic acid; strong acid monomers with, for example, sulfonic or phosphonic functions, such as vinyl sulfonic acid, vinyl phosphonic acid, allyl sulfonic acid, methylallyl sulfonic acid, 2-methylene propane-1,3-disulfonic acid, 2-sulfoethyl methacrylate, sulfopropyl methacrylate, sulfopropyl acrylate, allyl phosphonic acid, ethylene glycol methacrylate phosphate ester, 2-acrylamido-2-methylpropane sulfonic acid (ATBS), 2-acrylamido-2-methylpropane disulfonic acid, 3-allyloxy-2-hydroxypropane sulfonic acid, diethyl allyl phosphonate, carboxyethyl acrylate; water-soluble salts of these monomers, such as their alkali metal, alkaline earth metal or ammonium salts (other than the crystalline form of ATBS.Na), and mixtures thereof. Preferably, the one or more hydrophilic anionic monomers are acrylic acid and / or salts thereof.

[0190] The water-soluble polymer advantageously comprises from 1 to 100 mol%, preferably from 2 to 60 mol%, more preferably from 5 to 30 mol%, even more preferably from 5 to 20 mol% of one or more anionic hydrophilic monomers (other than the crystalline form of ATBS.Na), these percentages including the monomer of the crystalline form of ATBS.Na.

[0191] In one particular embodiment according to the application, the one or more hydrophilic anionic monomers other than the crystalline form of ATBS.Na can be salified.

[0192] By salified, we mean that at least one acid function of the anionic monomer of the type -R a (=0)-OH (R representing P, S or C) has its proton replaced by a metal or ammonium cation to form a salt of the type -R a (=0)-0X (X being a metal cation or an organic cation). In other words, the non-salified form corresponds to the acid form of the monomer, for example R b -C(=0)-OH in the case of a carboxylic function, while the salified form of the monomer corresponds to the form R b -C(=0)-0-X + , X +Corresponding to a basic cation or an organic cation. The acid functions of the branched water-soluble polymer can be partially or totally salified. The salified form advantageously corresponds to a salt of an alkali metal (Li, Na, K, etc.), an alkaline earth metal (calcium, magnesium, etc.) or an ammonium (for example an ammonium ion or a tertiary ammonium). The preferred salt is the sodium salt.

[0193] The salification can be carried out before, during or after polymerization.

[0194] In a particular embodiment according to the application, the water-soluble polymer advantageously comprises from 1 to 100 mol%, preferably from 20 to 100 mol%, more preferentially from 50 to 100 mol%, even more preferentially from 80 to 100 mol% of one or more hydrophilic anionic monomers in salified form. These percentages include the ATBS.Na monomer in crystalline form according to the application.

[0195] Advantageously, the one or more hydrophilic cationic monomers that can be used in the application are chosen from monomers derived from vinyl-type units (advantageously acrylamides, acrylic acids, allyl or maleic acids) having phosphonium or quaternary ammonium functions. The diallyldialkylammonium salts, for example diallyldimethylammonium chloride (DADMAC), can be mentioned in particular and in a non-limiting manner; acidified or quaternized salts of dialkylaminoalkyl (meth)acrylamides, for example methacrylamido-propyltrimethylammonium chloride (MAPTAC), acrylamido-propyltrimethylammonium chloride (APTAC); acidified or quaternized salts of dialkylaminoalkyl acrylates, for example quaternized or salified dimethylaminoethyl acrylate (DMAEA); acidified or quaternized salts of dialkylaminoalkyl methacrylates, for example quaternized or salified dimethylaminoethyl methacrylate (DMAEMA); acidified or quaternized salts of N,N-dimethylallylamine; acidified or quaternized salts of diallylmethylamine; acidified or quaternized salts of diallylamine; vinylamines obtained by hydrolysis (basic or acidic) of an amide group -N(R2)-CO-R1, in which R1 and R2 are independently a hydrogen atom or an alkylated chain of 1 to 6 carbons, for example a vinylamine obtained by hydrolysis of a vinylformamide; a vinylamine obtained by Hofmann degradation; and mixtures thereof. Advantageously, the alkyl groups are C1-C7, preferably C1-C3, and can be linear, cyclic, saturated or unsaturated chains. The quaternized dimethylaminoethyl acrylate is preferred.

[0196] The person skilled in the art knows how to prepare quaternized monomers, for example using a quaternizing agent of the R-X type (in which R is an alkyl group and X is a halogen or a sulfate).

[0197] The term "quaternizing agent" means a molecule capable of alkylating a tertiary amine.

[0198] The quaternizing agent can be chosen from dialkyl sulfate containing from 1 to 6 carbon atoms or a haloalkane containing from 1 to 6 carbon atoms. Preferably, the quaternizing agent is chosen from methyl chloride, benzyl chloride, dimethyl sulfate or diethyl sulfate. Furthermore, the present application also encompasses DADMAC, APTAC and MAPTAC monomers whose counterion is sulfate, fluoride, bromide or iodide instead of chloride.

[0199] The water-soluble polymer advantageously comprises from 0 to 20 mol%, preferably from 0 to 6 mol%, of one or more hydrophilic cationic monomers.

[0200] Advantageously, the one or more hydrophilic zwitterionic monomers can be derivatives of vinyl type units (advantageously acrylamide, acrylic acid, allyl or maleic acid) having a quaternary ammonium or ammonium function and a carboxylic acid (or carboxylate), sulfonic acid (or sulfonate) or phosphoric acid (or phosphate) function. Acryldimethylaminoethyl derivatives can be mentioned in particular and in a non-limiting manner, such as 2-((2-(acryloyloxy)ethyl)dimethylammonio)dimethylammonio)ethane-1 -sulfonate, 3-((2-(acryloyloxy)ethyl)dimethylammonio)propane-1 -sulfonate, 4-((2-(acryloyloxy)ethyl)dimethylammonio)butane-1 -sulfonate, [2-(acryloyloxy)ethyl](dimethylammonio)acetate, methacryldimethylaminoethyl derivatives, such as 2-((2-(methacryloyloxy)ethyl)dimethylamino)ethane-1 -sulfonate, 3-((2-(methacryloyloxy)ethyl)dimethylamino)propane-1 -sulfonate, 4-((2-(methacryloyloxy)ethyl)dimethylamino)butane-1 -sulfonate, [2-(methacryloyloxy)ethyl](dimethylamino)acetate, dimethylaminopropyl acrylamide derivatives, such as 2-((3-acrylamidopropyl)dimethylamino)ethane-1 -sulfonate, 3-((3-acrylamidopropyl)dimethylamino)propane-1 -sulfonate, 4-((3-acrylamidopropyl)dimethylamino)butane-1 -sulfonate, [3-(acryloyloxy)propyl](dimethylamino)acetate, dimethylaminopropyl methacrylamide derivatives, such as 2-((3-methacrylamidopropyl)dimethylamino)ethane-1 -sulfonate, 3-((3-methacrylamidopropyl)dimethylamino)propane-1 -sulfonate, 4-((3-methacrylamidopropyl)dimethylamino)butane-1 -sulfonate and [3-(methacryloyloxy)propyl](dimethylamino)acetate, and mixtures thereof.

[0201] Other hydrophilic zwitterionic monomers can be used, in particular those described by the Applicant in document WO 2021 / 123599.

[0202] The polymer advantageously comprises 0 to 20 mol%, more preferably 0 to 10 mol%, of one or more hydrophilic zwitterionic monomers.

[0203] Allocation coefficient K ow Hydrophobic monomers with a concentration greater than 1 can also be used to prepare the polymers according to the invention. They are preferably selected from the following list: those having (i) C4-C 30 Alkyl, or (ii) arylalkyl (C4-C5) 30 Alkyl, C4-C 30 (iii) aryl, or (iv) propoxylated, or (v) ethoxylated, or (v) ethoxylated and propoxylated chains of (meth)acrylates; alkyl aryl sulfonates (C4-C 30 Alkyl, C4-C 30 Aryl); with (i)C4-C 30 Alkyl, or (ii) arylalkyl (C4-C5) 30 Alkyl, C4-C 30 (iii) aryl, or (iv) propoxylated, or (v) ethoxylated, or (v) monosubstituted or disubstituted (meth)acrylamides with ethoxylated and propoxylated chains; anionic or cationic monomeric derivatives of (meth)acrylamide or (meth)acrylic acid with hydrophobic chains; vinylpyridine and mixtures thereof. The hydrophobic monomer may contain a halogen atom, such as chlorine.

[0204] Among these hydrophobic monomers:

[0205] -Alkyl group is preferably C4-C 20 More preferably, C4-C8. C6-C 20 Alkyl groups are preferably straight-chain, while C4-C5 alkyl groups are preferably branched.

[0206] -Arylalkyl group is preferably C7-C 25 More preferably C7-C 15 ,

[0207] The ethoxylated chain advantageously comprises 1 to 200, preferably 6 to 100, more preferably 10 to 40 -CH2-CH2-O- groups.

[0208] -The propoxylated chain advantageously comprises 1 to 50, more preferably 1 to 20 -CH2-CH2-CH2-O- groups.

[0209] Preferred hydrophobic monomers belonging to these categories are, for example:

[0210] n-hexyl (meth)acrylate, n-octyl (meth)acrylate, octyl (meth)acrylamide, lauryl (meth)acrylate, lauryl (meth)acrylamide, myristyl (meth)acrylate, myristyl (meth)acrylamide, pentadecyl (meth)acrylate, pentadecyl (meth)acrylamide, cetyl (meth)acrylate, cetyl (meth)acrylamide, oleyl (meth)acrylate, oleyl (meth)acrylamide, erucyl (meth)acrylate, erucyl (meth)acrylamide, N-tert-butyl (meth)acrylamide, 2-ethylhexyl acrylate, C4-C 22 itaconic acid half-ester, C4-C 22 acidified or quaternized salts of dialkylaminoalkyl esters, C4-C 22 acidified or quaternized salts of dialkylaminoalkyl (meth)acrylamides, vinylpyridine, acrylamidoundecanoic acid, and mixtures thereof,

[0211] - cationic allyl derivatives of formula (I) or (II):

[0212]

[0213] wherein:

[0214] R: independently an alkyl chain containing from 1 to 4 carbons;

[0215] R1: an alkyl or aralkyl chain containing from 8 to 30 carbons;

[0216] X: a halide selected from the group consisting of bromide, chloride, iodide, fluoride and any negatively charged counterion;

[0217] and preferably (meth)acryloyl-type hydrophobic cationic derivatives corresponding to formula (III):

[0218]

[0219] wherein:

[0220] - A represents O or N-R5 (preferably A represents N-R5),

[0221] - R2, R3, R4, R5, R6, R7: independently hydrogen or an alkyl chain containing from 1 to 4 carbons,

[0222] - Q: an alkyl chain containing from 1 to 20 carbons,

[0223] - R8: an alkyl or aralkyl chain containing from 8 to 30 carbons,

[0224] - X: halide selected from the group consisting of bromide, chloride, iodide, fluoride and any negatively charged counter-ion.

[0225] The water-soluble polymer advantageously comprises less than 5 mol% of hydrophobic monomers.

[0226] When the water-soluble polymer comprises hydrophobic monomers, they are present in an amount such that the polymer remains water-soluble.

[0227] Monomers with fluorescent functionality can also be used in the present application. Monomers with fluorescent functionality can be detected by any suitable method, for example by fluorimetry with a fixed wavelength fluorimeter. Typically, monomers with fluorescent functionality are detected at the excitation and emission maxima, which can be determined using a scanning fluorimeter.

[0228] Monomers with fluorescent functionality are selected from, for example, the following monomers: sodium or potassium styrene sulfonate, styrene sulfonic acid, vinyl imidazole and derivatives thereof, 9-vinyl anthracene and derivatives thereof, N-9-xanthenyl acrylamide and derivatives thereof, allyl dibenzosuberenol and derivatives thereof, chinconicin and derivatives thereof, quinophthalone and derivatives thereof, cinchoninone and derivatives thereof, N,N-dimethyl-N-[3-[N'-(4-m'thoxy naphthalimide)]]propyl-N-(2-hydroxy-3-allyloxy)propyl ammonium hydroxide and mixtures thereof.

[0229] When functionalised with an allyl, vinyl or acrylic double bond, other fluorescent compounds can be used, for example pyranine and derivatives thereof, coumarin and derivatives thereof, quinoxaline and derivatives thereof, pinacyanol and derivatives thereof, xanthene hydroxide and derivatives thereof, dabsyl and derivatives thereof, 3-hydroxy-2-methylene-3-(1-naphthyl)propionic acid and derivatives thereof, rhodamine and derivatives thereof, N-dibenzosuberyl acrylamide and derivatives thereof, naphthalene derivatives, fluorescein and derivatives thereof, pyrene and derivatives thereof, quinolone and derivatives thereof, pyrazoline and derivatives thereof and mixtures thereof.

[0230] In a preferred way, the polymer does not comprise monomers with fluorescent functionality.

[0231] In a particular embodiment according to the application, the water-soluble polymer can comprise at least one cyclic monomer having a hydrolysable functional group. Advantageously, the cyclic monomer(s) having a hydrolysable functional group is chosen from cyclic ketene acetals, thionolactones and mixtures thereof.

[0232] The cyclic ketene acetals are advantageously chosen from 2-methylene-1,3-dioxepane (MDO), 5,6-benzo-2-methylene-1,3-dioxepane (BMDO), 2-methylene-4-phenyl-1,3-dioxolane (MPDL), 2-methylene-1,3,6-trioxocane (MTC) and mixtures thereof. Preferably, it is 2-methylene-1,3-dioxepane (MDO).

[0233] The thionolactones are advantageously chosen from dibenzo[c,e]oxepine-7H-5-thione (DOT), ε-thio caprolactone, 3,3-dimethyl-2,3-dihydro-5H-benzo[e][1,4]dioxepine-5-thione (DBT) and mixtures thereof. Preferably, it is 3,3-dimethyl-2,3-dihydro-5H-benzo[e][1,4]dioxepine-5-thione.

[0234] In a particular embodiment according to the application, the water-soluble polymer can comprise at least one group having a LCST.

[0235] According to the common general knowledge of the person skilled in the art, a group having a LCST corresponds to a group whose water solubility is modified as a function of salinity above a certain temperature for a given concentration. It is a group having a thermal transition temperature defining its lack of affinity with the solvent medium. The lack of affinity with the solvent leads to opacity or loss of transparency, which can be due to precipitation, aggregation, gelation or viscosification of the medium. The lowest transition temperature is called LCST (Lower Critical Solution Temperature). For each concentration of the group having a LCST, a thermal transition temperature is observed. It is higher than the LCST, which is the lowest point on the curve. Below this temperature, the polymer is soluble in water; above this temperature, the polymer loses its solubility in water.

[0236] In a particular embodiment according to the application, the water-soluble polymer can comprise at least one group having a UCST.

[0237] According to the common general knowledge of the person skilled in the art, a group having a UCST corresponds to a group whose water solubility is changed as a function of salinity at a temperature lower than a specific temperature for a given concentration. It is a group having a cooling transition temperature defining its lack of affinity with the solvent medium. The lack of affinity with the solvent leads to opacity or loss of transparency, which can be due to precipitation, aggregation, gelation or viscosification of the medium. The highest transition temperature is called UCST (Upper Critical Solution Temperature). For each concentration of the group having a UCST, a cooling transition temperature is observed. It is lower than the UCST, which is the highest point on the curve. Above this temperature, the polymer is soluble in water; below this temperature, the polymer loses its solubility in water.

[0238] When preparing the water-soluble polymer, the amount of one or more different monomers will be adjusted by the person skilled in the art so as not to exceed 100 mol%.

[0239] Water-soluble polymer

[0240] The 2-acrylamido-2-methylpropane acid used to obtain the water-soluble polymer is advantageously at least 50 mol%, preferably 70 to 100 mol% of the sodium salt in crystalline form before polymerization. More preferably, 100 mol% of the ATBS is the sodium salt in crystalline form.

[0241] In a particular embodiment according to the application, the water-soluble polymer is advantageously obtained from 1 to 99 mol%, preferably 2 to 60 mol%, more preferably 5 to 30 mol%, even more preferably 5 to 20 mol% of one or more anionic hydrophilic monomers, these percentages including the ATBS.Na monomer in crystalline form.

[0242] In a particular embodiment according to the application, the water-soluble polymer can comprise 1 to 100 mol%, preferably 1 to 99 mol%, more preferably 2 to 60 mol%, more preferably 3 to 50 mol% of ATBS, advantageously at least 50 mol%, preferably 70 to 100 mol% of the ATBS used being the sodium salt in crystalline form, more preferably 100 mol% of the ATBS used being the sodium salt in crystalline form.

[0243] In a particular embodiment according to the application, the water-soluble polymer comprises 1 to 99 mol%, preferably 40 to 95 mol%, more preferably 45 to 90 mol% of non-ionic hydrophilic monomers; and 1 to 99 mol%, preferably 5 to 60 mol%, more preferably 10 to 55 mol% of ATBS, advantageously at least 50 mol%, preferably 70 to 100 mol% of the ATBS used being the sodium salt in crystalline form. Even more preferably, 100% of the ATBS used is the sodium salt in crystalline form.

[0244] In a preferred embodiment according to the application, the water-soluble polymer is a polymer based on acrylamide and ATBS, at least 50 mol% of the ATBS used being in the form of the sodium salt of the crystalline form. Preferably, the water-soluble polymer is a polymer consisting of acrylamide, acrylic acid and ATBS, at least 50 mol% of the ATBS used being in the form of the sodium salt of the crystalline form.

[0245] The polymer can be partially or totally post-hydrolyzed.

[0246] In a preferred embodiment according to the application, the water-soluble polymer is a polymer of ATBS sodium salt in the crystalline form and of an acrylic acid salt, or of ATBS sodium salt in the crystalline form and of a hydrolysable non-ionic monomer.

[0247] The hydrolysable non-ionic monomer is preferably chosen from acrylamide; methacrylamide; N-mono-derivatives of acrylamide or methacrylamide; N,N-derivatives of acrylamide or methacrylamide; and acrylate or methacrylate esters. Preferably, it is acrylamide.

[0248] According to the application, the water-soluble polymer can have a linear, branched, crosslinked, star or comb structure. These structures can be obtained according to the common general knowledge of the person skilled in the art, for example by choosing the initiator, the transfer agent, the polymerization technique (for example controlled radical polymerization known as RAFT (Reversible Addition-Fragmentation Transfer), NMP (Nitroxide-mediated Polymerization) or ATRP (Atom Transfer Radical Polymerization)), the incorporation of structural monomers, the concentration.

[0249] The water-soluble polymer can be further structured by a branching agent. The structured polymer is a nonlinear polymer with side chains, such that when dissolved in water, the polymer is highly entangled, which leads to a very high low-gradient viscosity.

[0250] The branching agent is advantageously chosen from:

[0251] - a structuring agent, which can be chosen from the group comprising polyethylenically unsaturated monomers (with at least two unsaturated functions), for example vinyl functions, in particular allyl or acrylic functions, and we can cite for example methylenebisacrylamide (MBA), triallylamine, or tetraallylammonium chloride or 1,2 dihydroxyethylene bis-(N-acrylamide),

[0252] - monomers with at least two epoxy functions,

[0253] - monomers with at least one unsaturated function and one epoxy function,

[0254] - macromolecular initiators, such as polyperoxides, polyazoids and transfer agents, such as polymercaptant polymers and polyols,

[0255] - functionalized polysaccharides,

[0256] - water-soluble metal complexes consisting of:

[0257] * a metal having a valence greater than 3, such as, but not limited to, aluminum, boron, zirconium or titanium, and

[0258] * a ligand bearing a hydroxyl function.

[0259] The amount of branching agent in the water-soluble polymer is advantageously less than 40,000 ppm, preferably less than 10,000 ppm, more preferably less than 5,000 ppm, relative to the total weight of monomers of the water-soluble polymer.

[0260] In a particular embodiment, the amount of branching agent is at least equal to 0.1 ppm, preferably at least 1 ppm, more preferably at least 10 ppm, more preferably at least 100 ppm, even more preferably at least 1000 ppm, relative to the total weight of monomers of the water-soluble polymer.

[0261] When the water-soluble polymer comprises a branching agent, the polymer can remain soluble in water. The person skilled in the art knows how to adjust the amount of branching agent and possibly of transfer agent necessary to obtain this result.

[0262] In a preferred embodiment according to the application, the water-soluble polymer does not comprise a branching agent.

[0263] In a particular embodiment, the water-soluble polymer can comprise a transfer agent.

[0264] The transfer agent is advantageously chosen from the following: methanol; isopropanol; sodium hypophosphite; calcium hypophosphite; magnesium hypophosphite; potassium hypophosphite; ammonium hypophosphite; formic acid; sodium formate; calcium formate; magnesium formate; potassium formate; ammonium formate; 2-mercaptoethanol; 3- mercapto propanol; dithiopropanol; thioglycerol; mercaptoacetic acid; mercaptopropionic acid; thiolactic acid; thiomalic acid; cysteine; aminoethanethiol; mercaptoacetate; allyl phosphites; allyl mercaptans, such as n-dodecyl mercaptan; sodium methylallyl sulfonate; calcium methylallyl sulfonate; magnesium methylallyl sulfonate; potassium methylallyl sulfonate; ammonium methylallyl sulfonate; alkyl phosphites, such as trialkyl(C 12 -C 15) esters, dioleyl hydrogen phosphite, dibutyl phosphite; dialkyldithiophosphoric acid esters, such as dioctyl phosphite; tertiary-nonyl mercaptan; 2-ethylhexyl mercaptoacetate; n-octyl mercaptan; n-dodecyl mercaptan; tertiary-dodecyl mercaptan; isooctyl mercaptoacetate; 2-ethylhexyl thioglycolate; 2-ethylhexyl mercaptoacetate; polythiols; and mixtures thereof. Sodium hypophosphite or sodium formate are preferred.

[0265] The amount of transfer agent in the water-soluble polymer is advantageously from 0 to 100,000 ppm, preferably from 0 to 10,000 ppm, more preferably from 0 to 1,000 ppm, even more preferably from 0 to 100 ppm, relative to the total weight of the polymer monomers. When a transfer agent is present, it is at least 0.1 ppm, preferably at least 1 ppm, relative to the total weight of the polymer monomers.

[0266] In a particular embodiment according to the application, the water-soluble polymer does not comprise a transfer agent.

[0267] Generally, the water-soluble polymer does not require any particular polymerization process to be developed. Indeed, it can be obtained using any polymerization technique well known to the person skilled in the art. These polymerization techniques include solution polymerization; gel polymerization; precipitation polymerization; emulsion polymerization (aqueous or inverse); suspension polymerization; reactive extrusion polymerization; water-in-water polymerization; or micellar polymerization.

[0268] The polymerization is generally a free-radical polymerization, preferably by inverse emulsion polymerization or gel polymerization. Free-radical polymerization includes free-radical polymerization using UV, azo, redox or thermal initiators, as well as controlled radical polymerization (CRP) or matrix polymerization techniques.

[0269] Controlled radical polymerization techniques include, but are not limited to, the following techniques: various variants of iodine transfer polymerization (ITP), nitroxide-mediated polymerization (NMP), atom transfer radical polymerization (ATRP), reversible addition fragmentation chain transfer (RAFT) polymerization (which includes the MADIX (macromolecular design by interchange of xanthate) technique), organometallic-mediated radical polymerization (OMRP) and organohetereoatom-mediated radical polymerization (OHRP).

[0270] As already indicated, the water-soluble polymer can be post-hydrolyzed. Post-hydrolysis is a hydrolysis reaction of the polymer after its formation by polymerization of one or more monomers. This step comprises reacting the hydrolysable function of the monomer, advantageously a non-ionic function, more advantageously an amide or ester function, with a hydrolysis agent. This hydrolysis agent can be an enzyme, an ion exchange resin, or an acid metal (for example a hydrohalide acid) or a base (e.g. an alkali metal hydroxide or an alkaline earth metal hydroxide). Preferably, the hydrolysis agent is a base. In the post-hydrolysis step of the water-soluble polymer, the number of carboxylic acid functions is increased. Indeed, the reaction between the base and the amide or ester functions present in the water-soluble polymer generates carboxylate groups.

[0271] When the preparation of the water-soluble polymer comprises a drying step (e.g. spray drying, drum drying, radiation drying such as microwave drying, or fluidized bed drying), the water-soluble polymer can be in liquid, gel or solid form.

[0272] The weight average molecular weight of the water-soluble polymer is advantageously at least 500,000 g / mol, preferably from 5 to 400 million g / mol, more preferably from 5 to 300 million g / mol. The molecular weight is defined as the weight average molecular weight.

[0273] The weight average molecular weight is determined from the intrinsic viscosity of the polymer. The intrinsic viscosity can be measured by methods known to the person skilled in the art and can be calculated from the specific viscosity values at different polymer concentrations by graphical extrapolation of the curve to zero concentration, by plotting the specific viscosity values (y-axis) against the concentrations (x-axis). The intrinsic viscosity values are plotted on the y-axis or using the least squares method. The molecular weight can then be determined using the Mark-Houwink equation:

[0274] [η] = K M α

[0275] where [η] represents the intrinsic viscosity of the polymer determined by solution viscosity method.

[0276] K represents an empirical constant.

[0277] M represents the molecular weight of the polymer.

[0278] a represents the Mark-Houwink coefficient.

[0279] K and a depend on the specific polymer-solvent system.

[0280] Fracturing fluid

[0281] The present invention relates to a fracturing fluid comprising an aqueous phase, at least one proppant and at least one water-soluble polymer of ATBS,

[0282] Before polymerization, the ATBS is ATBS.Na in the crystalline form described above.

[0283] The aqueous phase is advantageously chosen from seawater, brine and fresh water, and is advantageously brine.

[0284] Brines are solutions comprising water and organic or inorganic salts. The salts can include monovalent salts, divalent salts, trivalent salts and mixtures thereof. Advantageously, the brine comprises at least 1,000 mg / L, preferably at least 5,000 mg / L, more preferably at least 10,000 mg / L, even more preferably at least 50,000 mg / L of salts, and even more preferably the brine is saturated with salt.

[0285] The proppant can be chosen from the non-limiting list comprising sand, ceramic, bauxite, glass beads and resin impregnated sand.

[0286] Advantageously, the amount of proppant in the fracturing fluid is between 0.5 and 40% by weight, preferably between 1 and 25% by weight, more preferably between 1.5 and 20% by weight, relative to the total weight of the fracturing fluid.

[0287] Advantageously, the fracturing fluid comprises between 0.001 and 1% by weight, preferably between 0.002 and 0.2% of the water-soluble polymer obtained from ATBS.Na in crystalline form, relative to the total weight of the fracturing fluid.

[0288] The fracturing fluid can comprise other compounds known to the person skilled in the art, such as those cited in the document SPE 152596, for example:

[0289] - clay anti-swelling agents, such as potassium chloride or choline chloride, and / or

[0290] - bactericides, which are used to prevent the growth of bacteria, in particular sulfate-reducing bacteria, which can form sticky substances that reduce the surface of the channels. Examples include the most commonly used glutaraldehyde, or formaldehyde or isothiazolinone, and / or

[0291] - oxygen reduction agents, such as ammonium bisulfite, which are used to prevent the oxidation and corrosion of the injection pipes and the destruction of other components, and / or

[0292] - corrosion inhibitors, which are used to protect the pipes from oxidation by a residual amount of oxygen, preferably N,N dimethylformamide, and / or

[0293] - lubricants, such as petroleum distillates, and / or

[0294] - iron chelators, such as citric acid, EDTA (ethylenediaminetetraacetic acid), phosphonates and / or

[0295] - anti-fouling agents, such as phosphonates, phosphonates, polyacrylates or glycols.

[0296] Before use in the fracturing fluid, the water-soluble polymer according to the application can be in various solid or liquid forms. Preferably, it is in the form of a powder, a water-in-oil reverse emulsion, an aqueous multiphase granular suspension, or an oily multiphase granular suspension.

[0297] Method for preparing a fracturing fluid

[0298] The present invention also relates to a method for preparing a fracturing fluid by adding to water or brine at least one water-soluble polymer of ATBS.Na in crystalline form (as described above) and wherein the water-soluble polymer, before forming the fracturing fluid, is:

[0299] - in powder form;

[0300] - or in the form of a water-in-oil inverse emulsion;

[0301] - or in the form of an aqueous or oily multiphase granular suspension.

[0302] The method for preparing a fracturing fluid according to the present invention preferably comprises the step of adding to said fluid at least one proppant as described previously.

[0303] When the water-soluble polymer added to the fracturing fluid is in powder form before forming the fracturing fluid, the average size of the polymer particles is advantageously less than 1.5 mm, preferably less than 850 pm, more preferably less than 200 pm. The average size of the water-soluble polymer particles is advantageously greater than 5 pm.

[0304] The average size of the water-soluble polymer particles is the average size of the largest dimension, for example the diameter in the case of spherical particles. Advantageously, it is measured using a laser measuring device, using conventional techniques part of the knowledge of the person skilled in the art. For example, a Malvern Mastersizer, MS2000 can be used for this purpose. This type of equipment can be used to measure the particle size distribution of particles in liquid medium or in solid form by laser diffraction.

[0305] When the water-soluble polymer according to the present invention is in solid form, it can be partially or totally dissolved in water using a polymer preparation device such as the polymer slicing device (PSU) disclosed in EP 2 203 245.

[0306] When the water-soluble polymer added to the fracturing fluid is in the form of a water-in-oil inverse emulsion before forming the fracturing fluid, the concentration of water-soluble polymer in the emulsion is preferably between 5 and 60% by weight, more preferably between 15 and 40% by weight, relative to the weight of the emulsion.

[0307] In a preferred embodiment according to the present invention, the water-in-oil inverse emulsion can comprise between 0.01% and 70% by weight, preferably between 5% and 20%, of organic and / or inorganic salts relative to the weight of the emulsion. The salts can be chosen from the following non-limiting list: sodium chloride, sodium sulfate, sodium bromide, ammonium sulfate, ammonium chloride, lithium chloride, lithium bromide, potassium chloride, potassium bromide, magnesium sulfate, aluminum sulfate and mixtures thereof. The preferred salts are ammonium chloride and ammonium sulfate.

[0308] When the water-soluble polymer added to the fracturing fluid is in the form of an aqueous multiphase particulate suspension before the formation of the fracturing fluid, the suspension preferably comprises:

[0309] - 15 to 60% by weight of at least one water-soluble polymer in the form of solid particles having an average size of between 5 and 500 μιη;

[0310] - 15 to 45% by weight of at least one alkali metal salt and / or at least one alkaline earth metal salt;

[0311] - at least one viscosifying agent other than the water-soluble polymer;

[0312] - at least 10% by weight of water; and

[0313] the Brookfield viscosity of the suspension at a temperature of 20°C is between 500 and 20,000 cps; and

[0314] the density of the suspension is between 1.1 and 2 kg.L -1 .

[0315] When the water-soluble polymer added to the fracturing fluid is in the form of an oily multiphase particulate suspension before the formation of the fracturing fluid, the suspension preferably comprises:

[0316] - 15 to 60% by weight of at least one water-soluble polymer in the form of solid particles having an average size of between 5 and 500 μιη;

[0317] - at least one viscosifying agent other than the water-soluble polymer;

[0318] - at least 10% by weight of oil; and

[0319] the Brookfield viscosity of the suspension at a temperature of 20°C is between 500 and 20,000 cps; and

[0320] the density of the suspension is between 0.6 and 1.4 kg.L -1 .

[0321] The Brookfield viscosity is measured with a Brookfield device equipped with an LV module, which is able to rotate at a speed of 30 rpm, for example, the measurement advantageously being carried out at 20°C. The density is measured at a pressure of 1 atm (i.e. 101,325 Pa) at 20°C.

[0322] Method for hydraulic fracturing of unconventional subterranean petroleum or natural gas reservoirs

[0323] The present invention also relates to a method for hydraulic fracturing of unconventional subterranean petroleum or natural gas reservoirs, the method comprising preparing a fracturing fluid as described previously and injecting said fracturing fluid into a subterranean reservoir.

[0324] The injection is performed under pressure so as to create fractures distributed along the entire length of the production well.

[0325] Optionally, at least one oxidizing compound and / or at least one surfactant compound is injected into the reservoir before, during or after the creation of the fractures.

[0326] The injection of surfactant compounds helps to eliminate the viscosity created by the polymer by inhibiting the hydrophobic chain-chain interactions, while the injection of oxidizing compounds destroys the polymer. In both cases, the injection allows the fluid viscosity close to water to be re-established.

[0327] The oxidizing compounds include bleaching agents (aqueous solutions of hypochlorite), hydrogen peroxide, ozone, chloramine, persulfate, permanganate and perchlorate.

[0328] The chemical nature of the surfactant compound(s) is not critical. They can be anionic, non-ionic, amphoteric, zwitterionic and / or cationic. The surfactant compound(s) of the application preferably carry an anionic charge.

[0329] Preferably, the surfactant compound used is chosen from anionic surfactants and zwitterions thereof chosen from the group comprising derivatives of alkyl sulfates, alkyl ether sulfates, aryl alkyl sulfates, aryl alkyl ether sulfates, alkyl sulfonates, alkyl ether sulfonates, aryl alkyl sulfonates, aryl alkyl ether sulfonates, alkyl phosphates, alkyl ether phosphates, aryl alkyl phosphates, aryl alkyl ether phosphates, alkyl phosphonates, alkyl ether phosphonates, aryl alkyl phosphonates, aryl alkyl ether phosphonates, alkyl carboxylates, alkyl ether carboxylates, aryl alkyl ether carboxylates, aryl alkyl ether carboxylates, polyalkyl ethers, aryl alkyl polyethers, etc.

[0330] An alkyl chain is defined as a chain of 6 to 24 carbons, branched or unbranched, with or without multiple units, which can optionally include one or more heteroatoms (O, N, S). An aryl chain is defined as a chain of 6 to 24 carbons, branched or unbranched, comprising one or more aromatic rings and which can include one or more heteroatoms (O, N, S).

[0331] For reasons of cost, stability and availability, the most commonly used surfactant compounds are in the form of alkali metal or ammonium salts of sulfonate or sulfate type.

[0332] Method for reducing the friction of fracturing fluids in the operation of hydraulic fracturing of unconventional subterranean petroleum or natural gas reservoirs

[0333] The present invention also relates to a method of reducing friction of a fracturing fluid in the operation of hydraulically fracturing a subterranean reservoir of unconventional oil or gas, the method comprising preparing a fracturing fluid as previously described and injecting the fracturing fluid into the subterranean reservoir.

[0334] Reducing friction reduces or eliminates losses (pressure) due to friction during the process of injecting a fracturing fluid. The present invention and its advantages will become apparent from the following embodiments. BRIEF DESCRIPTION OF DRAWINGS

[0335] Figure 1 A proton NMR spectrum of ATBS needle crystals obtained according to Example 1 is shown.

[0336] Figure 2 A proton NMR spectrum of ATBS.Na crystals obtained according to Example 2a is shown.

[0337] Figure 3 An X-ray diffraction pattern of ATBS crystals obtained according to Example 1 is shown.

[0338] Figure 4 An X-ray diffraction pattern of ATBS.Na crystals obtained according to Example 2a is shown.

[0339] Figure 5 A Fourier transform infrared spectrum of ATBS crystals obtained in Example 1 is shown.

[0340] Figure 6 A Fourier transform infrared spectrum of ATBS.Na crystals obtained in Example 2a is shown.

[0341] Figure 7 A thermogram of ATBS crystals obtained according to Example 1 is shown.

[0342] Figure 8 A thermogram of ATBS.Na crystals obtained according to Example 2a is shown.

[0343] Figure 9 A percent friction reduction of a post-hydrolyzed polymer is shown as a function of time.

[0344] Figure 10 A percent friction reduction of a terpolymer is shown as a function of time.

[0345] Figure 11 A percent friction reduction of a homopolymer is shown as a function of time.

[0346] Figure 12 A percent friction reduction of a copolymer is shown as a function of time.

[0347] Figure 13An optical microscope view of ATBS needle crystals obtained according to Example 1 is shown.

[0348] Figure 14 An optical microscope view of ATBS.Na crystals obtained according to Example 2a is shown.

[0349] Figure 15 An optical microscope view of ATBS.Na crystals obtained according to Example 2b is shown.

[0350] Figure 16 An optical microscope view of ATBS.Na crystals obtained according to Example 2c is shown.

[0351] Figure 17 A photo of the ATBS.Na product obtained in solution according to Comparative Example 2b is shown.

[0352] Figure 18 An optical microscope view of ATBS.Na crystals obtained according to Comparative Example 2c is shown.

[0353] Figure 19 An optical microscope view of ATBS.Na crystals obtained according to Comparative Example 2d is shown.

[0354] Figure 20 An optical microscope view of ATBS.Na crystals obtained according to Comparative Example 2e is shown. DETAILED DESCRIPTION

[0355] Example

[0356] Example 1 : Synthesis of 2-acrylamido-2-methylpropane sulfonic acid (ATBS) (A H ) from acrylonitrile

[0357] To a stirred double-jacketed 2000 ml reactor containing 1522 g of acrylonitrile with 0.4 wt% water, the mixture was stirred for 1 h and cooled through the double-jacket of the reactor which maintained the temperature of the sulfonation mixture at -20°C, then 180 g of oleum with a titration of 104% H2SO4(18% fuming sulfuric acid) was added.

[0358] 97 g of isobutene was added to the previous sulfonation mixture at a rate of 1.6 g / min.

[0359] The temperature of the mixture was controlled at 45°C when isobutene was added. The particles of 2-acrylamido-2-methylpropanesulfonic acid precipitated from the mixture with a solid content of about 20% by weight. The reaction mixture was filtered through a Buchner funnel and dried under vacuum at 50°C. The solid obtained was 2-acrylamido-2-methylpropanesulfonic acid (ATBS A H ) in the form of a very fine white powder.

[0360] Optical microscopy observations ( Figure 13 ) show that ATBS A H crystals have a needle-like morphology.

[0361] Example 2a: formation of 2-acrylamido-2-methylpropanesulfonic acid sodium salt (ATBS.Na A Na 2a) in crystalline form (application)

[0362] A solution of 439 g of sodium hydroxide 22% by weight in water was added to a double-jacketed 1000 ml reactor stirred. 452 g of ATBS A H 2a of example 1 were added to the previous mixture.

[0363] The mixture was stirred at 10°C for 30 min to form an aqueous solution SA2.

[0364] The aqueous solution SA2 was heated to a temperature of 40°C under vacuum at 50 mbar for 20 minutes then the temperature was maintained at 50 mbar for 30 minutes and cooled to a temperature of 10°C. The cooling time was 6h from 40°C to 10°C. A suspension S1 of ATBS.Na A Na 2a crystals was obtained. The suspension S1 was filtered on a Robatel vertical centrifuge. A solid of composition C1 containing 80% by weight of ATBS.Na A

[0365] Optical microscopy observations ( Figure 14 ) show that ATBS.Na A Na 2a crystals have a columnar and platelet-like morphology.

[0366] Example 2b: formation of ATBS sodium salt (ATBS.Na A Na 2b) in crystalline form

[0367] ATBS.Na A Na 2b crystals were prepared according to the procedure described in example 2a, except that SA2 was distilled at 700 mbar.

[0368] Optical microscopy observations ( Figure 15 ) show that ATBS.Na A Na2b crystals are identical to ATBS.Na A prepared in example 2a Na 2a crystals are identical.

[0369] Example 2c: ATBS sodium salt in crystalline form (ATBS.Na A Na 2c) formation

[0370] ATBS.Na A was prepared according to the procedure described in example 2a Na 2c crystals, except that the cooling time was reduced to 3h45.

[0371] Optical microscope observation Figure 16 showed that the crystals obtained under these conditions were identical to ATBS.Na A prepared in example 2a Na 2a crystals.

[0372] Comparative example 2a: preparation of ATBS.Na crystals (CE-A Na 2a) (not obtained)

[0373] The reaction was performed according to the procedure described in example 2a, except that SA2 was distilled under atmospheric pressure.

[0374] At the end of the cooling step, the aqueous solution SA2 did not allow the formation of a suspension S1 and no filtration or centrifugation operation could be performed to isolate ATBS sodium salt crystals.

[0375] Comparative example 2b: preparation of ATBS sodium salt crystals (CE-A Na 2b) (not obtained)

[0376] The reaction was performed according to the conditions described in example 27 of patent application US6331647.

[0377] 124 g of sodium hydroxide and 0.13 g of hydroquinone monomethyl ether were added to a stirred double-jacket 5000 ml reactor containing 400 g of water. The medium was stirred until the total dissolution of the sodium hydroxide.

[0378] 632 g of ATBS A H were added to the previous mixture. The mixture was stirred at 10°C for 30 min to form a 2-acrylamido-2-methylpropanesulfonic acid sodium salt aqueous solution.

[0379] The obtained aqueous solution was filtered in a 3000 ml reactor equipped with a distillation apparatus and containing an air scrubbing tube. The content was heated and stirred while air was blown on the surface at a rate of 0.5 cubic feet / hour. The content was heated to 50°C under vacuum at 933 mbar (~ 700 mm Hg). As the water was removed, a light yellow honey-like product was formed. The product was then transferred to a Robatel vertical centrifuge, but no solid was recovered.

[0380] As no solid was obtained, optical microscopy observation Figure 17 ) was not possible.

[0381] Comparative Example 2c: Preparation of ATBS sodium salt crystals (CE-A Na 2c) (not obtained)

[0382] The reaction was performed according to the conditions described in Example 3 of patent application WO2013079507.

[0383] 100 g of ATBS.Na solution (16.77 wt%) were obtained according to Example 1 of WO2013079507.

[0384] 50 g of solvent (mixture of acrylonitrile and methanol) were removed from the ATBS.Na solution at room temperature under reduced pressure (less than 700 mbar) while air was introduced into the ATBS.Na solution. ATBS.Na CE-A Na 2c solid was formed, filtered and washed with acrylonitrile / methanol and then dried overnight at 50°C.

[0385] Optical microscopy observation Figure 18 ) showed that the dried solid of ATBS.Na CE-A Na 2c did not correspond to ATBS.Na crystals according to the application.

[0386] Comparative Example 2d: Preparation of ATBS.Na CE-A Na 2d (not according to the application)

[0387] The reaction was performed according to the procedure described in Example 2a, except that SA2 was distilled at 720 mbar.

[0388] A solid of composition CI was obtained, containing 80 wt% of ATBS.Na CE-A Na 2d crystals.

[0389] Optical microscopy observation Figure 19 ) showed that the crystals of ATBS.Na CE-A Na 2c did not correspond to ATBS.Na crystals according to the application.

[0390] Comparative Example 2e: ATBS.Na CE-A Na Preparation of 2e (not according to the invention)

[0391] The reaction was carried out according to the procedure described in Example 2a, except that the cooling time was 3h20.

[0392] A solid composition C1 was obtained, containing 80% by weight of ATBS.Na CE-A Na 2e crystals.

[0393] Optical microscopy observation Figure 20 ) shows ATBS.Na CE-A Na 2e crystals do not correspond to ATBS.Na crystals according to the invention.

[0394] Example 3: ATBS A of Examples 1 and 2a H and ATBS.Na A Na NMR analysis of the product of 2a

[0395] ATBS A H and ATBS.Na A Na 2a was analyzed by proton nuclear magnetic resonance (NMR).

[0396] The sample was dissolved in D2O. The NMR machine was a Bruker model at a frequency of 400 MHz, equipped with a 5 mm BBO BB- 1 H.

[0397] The two proton spectra Figure 1 and 2 are similar, with peak assignments consistent with the molecular structure of ATBS or sodium salt.

[0398] Example 4: ATBS A of Examples 1 and 2a H and ATBS.Na A Na X-ray diffraction analysis of the product of 2a

[0399] ATBS A H and ATBS.Na A Na 2a crystals were previously ground to form a powder, analyzed by X-ray diffraction over an angular range of 10 to 90°. The equipment used was a Rigaku MiniFlex II diffractometer equipped with a copper source.

[0400] ATBS.Na A Na 2a crystals Figure 4) showing an X-ray diffractogram with the following characteristic peaks: 11.7°; 12.2°; 13.2°; 13.5°; 15.6°; 16.8°; 17.8°; 18.5°; 19.1°; 20.6°; 21.4°; 23.3°; 25.1°; 25.8°; 26.9°; 29.1°; 29.5°; 31.0°; 33.0°; 33.6°; 34.4°; 35.2°; 35.9°; 37.1°; 38.4°; 39.6°; 41.1°; 42.9°; 45.1°; 46.0°; 47.2°; 47.6°, 2-theta angle (+ / - 0.1°).

[0401] ATBS A H showing an X-ray diffractogram with the following characteristic peaks: 11.7°; 12.2°; 13.2°; 13.5°; 15.6°; 16.8°; 17.8°; 18.5°; 19.1°; 20.6°; 21.4°; 23.3°; 25.1°; 25.8°; 26.9°; 29.1°; 29.5°; 31.0°; 33.0°; 33.6°; 34.4°; 35.2°; 35.9°; 37.1°; 38.4°; 39.6°; 41.1°; 42.9°; 45.1°; 46.0°; 47.2°; 47.6°, 2-theta angle (+ / - 0.1°). Figure 3 ) do not have the same peaks.

[0402] Example 5: ATBS A H and ATBS.Na A Na 2a

[0403] The equipment used for the Fourier transform infrared measurement was a Perkin Elmer Spectrum 100, equipped with a single reflection ATR polarized accessory, with a precision of 8 cm -1 .

[0404] ATBS A H and ATBS.Na A Na 2a crystals were sieved to 100 pm. The particles left on the sieve were dried and placed in an oven at 60°C for at least 4 hours.

[0405] Hundreds of milligrams of solid were placed on the diamond of the ATR accessory, with manual application of pressure with the accessory.

[0406] The following bands Figure 6 are characteristic of the crystalline form of ATBS.Na A Na 2a: 3576 cm -1 , 3485 cm -1 , 3310 cm -1 , 3079 cm -1 , 2975 cm -1 , 1658 cm -1 , 1629 cm -1 , 1543 cm -1 , 1403 cm -1 , 1321 cm -1 , 1301 cm -1 , 1205 cm -1 , 1187 cm -1 , 1163 cm-1 , 1046 cm -1 , 980 cm -1 , 629 cm -1 .

[0407] ATBS A H The infrared spectrum of the product of Example 1 and 2a Figure 5 does not have the same peaks.

[0408] Example 6: ATBS A H and ATBS.Na A Na 2a product

[0409] The equipment used was a Mettler DSC 3.

[0410] ATBS A H and AATBS.Na A Na 2a crystals were analyzed under a nitrogen flow at a heating rate of 10 °C / min. The initial temperature was 30 °C and the product was heated to 350 °C.

[0411] ATBS A H The thermogram of the product of Example 1 and 2a Figure 7 shows a thermal effect at a temperature of 195.15 °C, which is generally considered to be the melting point / degradation point of ATBS, followed by two exothermic degradation phenomena at 212.8 °C and 288.4 °C.

[0412] ATBS.Na A Na 2a crystals Figure 8 shows 4 thermal phenomena at 49.8 °C; 144.8 °C; 169.8 °C; and 254.3 °C.

[0413] Example 7: Polymers PI, P3, P5 and P7 synthesized according to the application and comparative polymers P2 (CE), P4 (CE), P6 (CE) and P8 (CE)

[0414] Example 7a: Post-hydrolysis polymers P1 and P2 / P2c-e (CE) of ATBS / acrylamide (AM)

[0415] Synthesis of polymer 1 PI (according to the application)

[0416] 761.9 g of deionized water, 574.2 g of acrylamide (50% by weight aqueous solution), 11.7 g of urea and 103.2 g of ATBS.Na A Na 2a crystals were added to a 2000 mL beaker.

[0417] The resulting solution was cooled to 0 to 5 °C and transferred to an adiabatic polymerization reactor. Nitrogen was bubbled for 30 minutes to eliminate any traces of dissolved oxygen.

[0418] Then the following substances were added to the reactor:

[0419] - 0.45 g 2,2’-azobisisobutyronitrile,

[0420] - 1.5 mL of a 5 g / L solution of 2,2’-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride,

[0421] - 1.5 mL of a 1 g / L solution of sodium hypophosphite,

[0422] - 2.25 ml of a 1 g / L solution of tert-butyl hydroperoxide,

[0423] - 3.0 ml of a 1 g / L solution of ammonium sulfate and iron(II) sulfate hexahydrate (molar salt).

[0424] After a few minutes, the nitrogen inlet was closed and the reactor was closed. The polymerization reaction was carried out for 1 to 5 hours until the temperature peak was reached. The obtained gel was cut into particles of 1 to 6 mm in size.

[0425] Post-hydrolysis of acrylamide : Then 500.0 g of the previously cut gel was mixed with 22.5 g of a 50% sodium hydroxide solution. The mixture was heated and maintained at a temperature of 90°C for 90 minutes.

[0426] The gel was then dried and ground to obtain the polymer P1 in powder form.

[0427] Synthesis of the comparative polymer P2 and P2c to P2e (CE)

[0428] Polymer 2 (CE) was obtained according to the protocol described for P1 with 93.1 g of ATBS A H and 36 g of sodium hydroxide at a concentration of 50% by weight in water instead of ATBS.Na A Na 2a.

[0429] Polymers P2c to P2e (CE) were prepared according to the protocol described for P1 with respectively CE-A Na 2c, CE-A Na 2d and CE-A Na 2e instead of ATBS.Na A Na 2a.

[0430] Example 7b: Terpolymer P3 (according to the application) and comparative polymer P4 / P4c-e (CE) of acrylic acid (AA) / ATBS / AM Example 7c: Homopolymer P5 (according to the application) and comparative polymer P6 / P6c-e (CE) of ATBS

[0431] Polymer 3 P3 was prepared according to the protocol described for PI using 1022 g of deionized water, 558.7 g of a 50% solution of acrylamide, 89 g of a 50% solution of sodium hydroxide, 80 g of ice acrylic acid, 15.3 g of urea and 125 g of ATBS.Na A Na 2a was obtained.

[0432] Comparative polymer 4 P4 (CE) was prepared according to the protocol described for P3 using 93.1 g of ATBS A H and 36 g of sodium hydroxide in water at a concentration of 50% by weight instead of ATBS.Na A Na 2a was obtained.

[0433] Comparative polymers P4c to P4e (CE) were prepared according to the protocol described for P3 using respectively CE-A Na 2c, CE-A Na 2d and CE-A Na 2e instead of ATBS.Na A Na 2a was prepared.

[0434] Example 7d: Polymer P7 (according to the application) and comparative polymer P8 / P8c-e of ATBS / AM

[0435] Polymer 5 P5 was prepared according to the protocol described for PI using 800 g of deionized water and 500 g of ATBS.Na A Na 2a.

[0436] Comparative polymer 6 P6 (CE) was prepared according to the protocol described for PI using 93.1 g of ATBS A H and 36 g of sodium hydroxide in water at a concentration of 50% by weight instead of ATBS.Na A Na 2a was obtained.

[0437] Comparative polymers P6c to P6e (CE) were prepared according to the protocol described for PI using respectively CE-A Na 2c, CE-A Na 2d and CE-A Na 2e instead of ATBS.Na A Na 2a was prepared.

[0438] Figures 9 to 12

[0439] Polymer 7 P7 was prepared according to the protocol described for PI using 1035 g of deionized water, 520.5 g of a 50% solution of acrylamide, 16.2 g of urea and 285 g of ATBS.Na A Na 2a was prepared.

[0440] Polymer 8 P8 (CE) was prepared according to the protocol described for PI using 93.1 g of ATBS AH and 36 g of sodium hydroxide in water at a concentration of 50% by weight instead of ATBS.Na A Na 2a obtained.

[0441] Polymers P8c to P8e (CE) were prepared according to the protocol described for PI using CE-A Na 2c, CE-A Na 2d and CE-A Na 2e instead of ATBS.Na A Na 2a prepared.

[0442] Example 8: Preparation of Fracturing Fluid

[0443] The pre-prepared polymers in powder form were dissolved in brine under stirring at a concentration of 10,000 ppm (weight) per liter of the brine, which consisted of water, 85 g of sodium chloride (NaCI) and 33.1 g of calcium chloride (CaCI2, 2H2O).

[0444] The resulting polymer salt solution was then injected into the circulating brine at a concentration of 0.05 pptg (parts per thousand gallons) for subsequent flow loop testing.

[0445] Example 9: Flow Loop Friction Reduction Testing

[0446] To evaluate the friction reduction of each polymer, the flow loop tank was filled with 20 L of brine (the brine described in Example 5). The brine was then recirculated through the flow loop at a rate of 24 gallons per minute (1 gallon = 3.78541 liters). The polymer was added to the recirculating brine at a concentration of 0.5 pptg. The percent friction reduction was determined by measuring the change in pressure within the flow loop.

[0447] The results are shown in ​ .

[0448] The results show that injection fluids prepared using polymers according to the present application provide improved friction reduction. The use of ATBS.Na crystals according to the present application to prepare ATBS-based polymers PI, P3, P5 and P7 therefore results in better friction reducing performance of the fluids.

Claims

1. Fracturing fluid comprising at least one aqueous phase, proppants and at least one water-soluble polymer of 2-acrylamido-2-methylpropane sulfonic acid, 2-Acrylamido-2-methylpropane sulfonic acid is, before polymerization, 2-acrylamido-2-methylpropane sulfonic acid sodium salt in crystalline form having a powder X-ray diffraction pattern comprising peaks at the following positions: 11.7°; 12.2°; 13.2°; 13.5°; 15.6°; 16.8°; 17.8°; 18.5°; 19.1°; 20.6°; 21.4°; 23.3°; 25.1°; 25.8°; 26.9°; 29.1°; 29.5°; 31.0°; 33.0°; 33.6°; 34.4°; 35.2°; 35.9°; 37.1°; 38.4°; 39.6°; 41.1°; 42.9°; 45.1°; 46.0°; 47.2°; 47.6°, degrees 2-theta.

2. The fracturing fluid of claim 1, wherein, At least 50 mol% of the 2-acrylamido-2-methylpropane sulfonic acid of the water-soluble polymer is, before polymerization, sodium salt in crystalline form.

3. The fracturing fluid of claim 1, wherein, The water-soluble polymer is a polymer of 2-acrylamido-2-methylpropane sulfonic acid sodium salt in crystalline form and at least one hydrophilic monomer selected from non-ionic monomers, anionic monomers, cationic monomers, zwitterionic monomers and mixtures thereof.

4. The fracturing fluid of claim 1 or 3, wherein, The water-soluble polymer comprises from 1 to 100 mol% of 2-acrylamido-2-methylpropane sulfonic acid, at least 50 mol% of the 2-acrylamido-2-methylpropane sulfonic acid being, before polymerization, sodium salt in crystalline form.

5. The fracturing fluid of any of the preceding claims, wherein, The water-soluble polymer is a polymer of 2-acrylamido-2-methylpropane sulfonic acid sodium salt in crystalline form and of an acrylic acid salt, or an anionic polymer of 2-acrylamido-2-methylpropane sulfonic acid sodium salt in crystalline form and of a hydrolysable non-ionic monomer.

6. The fracturing fluid of any of the preceding claims, wherein, The fracturing fluid comprises from 0.001 to 1% by weight of water-soluble polymer relative to the total weight of the fracturing fluid.

7. Process for the preparation of a fracturing fluid according to any one of the preceding claims, by adding to water or brine at least one water-soluble polymer of 2-acrylamido-2-methylpropane sulfonic acid sodium salt in crystalline form, and wherein the water-soluble polymer is in the form, before forming the fracturing fluid: - in the form of a powder; - or in the form of a water-in-oil inverse emulsion; - or in the form of an aqueous or oily multiphase granular suspension, The crystalline form of sodium salt of 2-acrylamido-2-methylpropane sulfonic acid has an X-ray powder diffraction pattern comprising peaks at the following positions: 11.70°; 12.20°; 13.2°; 13.5°; 15.60°; 16.80°; 17.80°; 18.5°; 19.1°; 20.6°; 21.40°; 23.3°; 25.1°; 25.8°; 26.9°; 29.10°; 29.50°; 31.0°; 33°; 33.6°; 34.4°; 35.2°; 35.9°; 37.1°; 38.4°; 39.6°; 41.10°; 42.90°; 45.10°; 46.0°; 47.2°; 47.6° degrees 2-theta.

8. The method of claim 7, wherein, The water-soluble polymer is in the form of a powder before forming the fracturing fluid, the average polymer particle size being less than 1.5 mm.

9. The method of claim 7, wherein, The fracturing fluid is in the form of a water-in-oil inverse emulsion before forming the fracturing fluid, the concentration of water-soluble polymer in the emulsion preferably being between 5 and 60% by weight relative to the weight of the emulsion.

10. The method according to any one of claims 7 to 9, characterized in that, The water-in-oil inverse emulsion comprises between 0.01 and 70% by weight of organic and / or inorganic salts relative to the weight of the emulsion.

11. The method according to any one of claims 7 to 10, characterized in that, The water-soluble polymer is in the form of an aqueous multiphase particle suspension before forming the fracturing fluid, comprising: - between 15 and 60% by weight of at least one water-soluble polymer in the form of solid particles having an average size of between 5 and 500 μιη; - between 15 and 45% by weight of at least one alkali metal salt and / or at least one alkaline earth metal salt; - at least one viscosifying agent other than the water-soluble polymer according to the application; - at least 10% by weight of water; and The Brookfield viscosity of the suspension at a temperature of 20°C is between 500 and 20,000 cps; and The density of the suspension is between 1.1 and 2 kg.L -1 .

12. The method according to one of claims 7 to 10, characterized in that, The water-soluble polymer is in the form of an oily multiphase particle suspension before forming the fracturing fluid, comprising: - between 15 and 60% by weight of at least one water-soluble polymer in the form of solid particles having an average size of between 5 and 500 μιη; - at least one viscosifying agent other than the water-soluble polymer according to the application; - at least 10% by weight of oil; and The Brookfield viscosity of the suspension at a temperature of 20°C is between 500 and 20,000 cps; and The density of the suspension is between 0.6 and 1.4 kg.L -1 .

13. A method for hydraulic fracturing of an unconventional subterranean oil or gas reservoir, the method comprising preparing a fracturing fluid according to any one of claims 1 to 6 and injecting the fracturing fluid into the subterranean reservoir.

14. A method for reducing the friction of a fracturing fluid in the operation of hydraulic fracturing of an unconventional subterranean oil or gas reservoir, the method comprising preparing a fracturing fluid according to any one of claims 1 to 6 and injecting the fracturing fluid into the subterranean reservoir.

Citation Information

Patent Citations

  • Device for preparing a dispersion of water-soluble polymers in water, and method implementing the device

    EP2203245A1

  • Hydraulic fracturing

    US3727689A

  • Fracturing with radiation-induced polymers

    US3841402A

  • Fracturing fluid

    US3938594A

  • High temperature guar-based fracturing fluid

    US4801389A